Thermal conductivity modifier and molded article

JP7916895B2Active Publication Date: 2026-09-08ZEON CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023502419
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-02-26
Filing Date
2022-02-22
Publication Date
2026-09-08
Estimated Expiration
2042-02-22

AI Technical Summary

Benefits of technology

【0014】 上記の如き本開示の熱伝導率調整剤によれば、ワニスを用いて形成される成形体等の熱伝導率を低減することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007916895000004
    Figure 0007916895000004
  • Figure 0007916895000005
    Figure 0007916895000005
  • Figure 0007916895000001
    Figure 0007916895000001
Patent Text Reader

Abstract

The present invention provides: a thermal conductivity regulating agent in the form of hollow particles, the thermal conductivity regulating agent being capable of decreasing the thermal conductivity of a molded body that uses a varnish as a starting material, and the like; and a molded body which contains this thermal conductivity regulating agent and has a decreased thermal conductivity. A thermal conductivity regulating agent that is in the form of hollow particles, each of which comprises a shell containing a resin and a hollow part surrounded by the shell, wherein: the shell contains, as the resin, a polymer that contains 80 parts by mass or more of a crosslinkable monomer unit in 100 parts by mass of all the monomer units; and with respect to an immersion test of the thermal conductivity regulating agent, in which 0.1 mg of the thermal conductivity regulating agent is added to 4 mL of acetone in an environment of 25°C, shaken for 10 minutes at a shaking speed of 100 rpm, and subsequently left at rest for 48 hours, the amount of the thermal conductivity regulating agent that settled out in the acetone is less than 5% by mass.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to a thermal conductivity modifier in the form of hollow particles, and a molded article containing the thermal conductivity modifier. [Background technology]

[0002] Hollow particles (hollow resin particles) are particles with cavities inside. Compared to solid particles that are substantially filled with resin, they scatter light well and have low light transmittance. Therefore, they are widely used as organic pigments and opacities with excellent optical properties such as opacity and whiteness in applications such as water-based paints and paper coating compositions. In recent years, hollow particles have been used not only in water-based paints and paper coating compositions, but also as lightweighting agents and heat insulating agents for resins and paints used in various fields such as automobiles, aerospace, electrical, electronics, and construction.

[0003] Patent Document 1 discloses a thermal conductivity modifier in the form of hollow particles having an average particle size of 10 to 150 nm and a gel fraction of 95% or more, with a shell containing a vinyl resin. Patent Document 1 states that by adding this thermal conductivity modifier, a film with low reflectivity can be produced.

[0004] On the other hand, the applicant has disclosed in Patent Document 2 hollow resin particles with excellent heat insulation properties, having a number-average particle size of 0.1 to 9.0 μm, a porosity of 70 to 99%, and a volatile organic compound content of 5% by mass or less. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] Japanese Patent Publication No. 2017-66351 [Patent Document 2] International Publication No. 2019 / 188996 [Overview of the project] [Problems that the invention aims to solve]

[0006] However, conventional thermal conductivity modifiers in the form of hollow particles, when added to molded articles made from solvent-containing resin compositions (varnishes), sometimes failed to maintain the voids within the particles, resulting in insufficient reduction of the thermal conductivity of the molded article. The object of this disclosure is to provide a thermal conductivity modifier in the form of hollow particles that can reduce the thermal conductivity of molded articles made from varnish, and a molded article containing the thermal conductivity modifier and having reduced thermal conductivity. [Means for solving the problem]

[0007] The inventors focused on the permeability of the shell of hollow particles to polar solvents and found that by adjusting the composition and formation method of the shell, hollow particles with a shell that is resistant to acetone penetration have excellent solvent resistance, are less prone to crushing, and maintain their particle shape even when a molded body is made using a varnish containing these hollow particles, thereby reducing the thermal conductivity of a molded body made from varnish.

[0008] This disclosure relates to a thermal conductivity modifier in the form of hollow particles comprising a resin-containing shell and a hollow portion surrounded by the shell, The shell contains a polymer as the resin, which contains 80 parts by mass or more of crosslinkable monomer units in 100 parts by mass of total monomer units. In an immersion test of a thermal conductivity modifier, in which 0.1 mg of the thermal conductivity modifier is added to 4 mL of acetone at 25°C, shaken at a shaking speed of 100 rpm for 10 minutes, and then allowed to stand for 48 hours, the amount of thermal conductivity modifier that precipitates in the acetone is less than 5% by mass.

[0009] In the thermal conductivity modifier of the present disclosure, the polymer contained in the shell further contains hydrophilic non-crosslinked monomer units derived from a hydrophilic non-crosslinked monomer having a solubility of 0.3 g / L or more in distilled water at 20°C, and preferably the content of the hydrophilic non-crosslinked monomer units is 2 to 20 parts by mass and the content of the crosslinked monomer units is 80 to 98 parts by mass per 100 parts by mass of the total monomer units of the polymer.

[0010] In the thermal conductivity modifier of the present disclosure, the polymer contained in the shell preferably contains, as the crosslinkable monomer units, three- or more crosslinkable monomer units derived from a three- or more-functional crosslinkable monomer, and the content of the three- or more-functional crosslinkable monomer units is 5 to 50 parts by mass per 100 parts by mass of the total monomer units of the polymer.

[0011] In the thermal conductivity modifier of this disclosure, it is preferable that the porosity is 50% or more.

[0012] In the thermal conductivity modifier of this disclosure, the volume-average particle size is preferably 1.0 to 30.0 μm.

[0013] This disclosure provides a molded article containing the thermal conductivity modifier described above. [Effects of the Invention]

[0014] According to the thermal conductivity modifier of this disclosure as described above, the thermal conductivity of molded articles and the like formed using varnish can be reduced. [Brief explanation of the drawing]

[0015] [Figure 1] This figure illustrates an example of a method for manufacturing the thermal conductivity modifier of this disclosure. [Figure 2] This is a schematic diagram showing one embodiment of a suspension in the suspension process. [Modes for carrying out the invention]

[0016] In the present disclosure, the symbol "~" used in a numerical range means that the numerical values described before and after it are included as the lower limit and the upper limit, respectively. In addition, in the present disclosure, (meth)acrylate refers to both acrylate and methacrylate; (meth)acrylic refers to both acrylic and methacrylic; and (meth)acryloyl refers to both acryloyl and methacryloyl. Furthermore, in the present disclosure, a polymerizable monomer is a compound having a functional group capable of addition polymerization (which may be simply referred to as a polymerizable functional group in the present disclosure). In the present disclosure, a compound having an ethylenically unsaturated bond as a functional group capable of addition polymerization is generally used as the polymerizable monomer. Polymerizable monomers include non-crosslinkable monomers and crosslinkable monomers. A non-crosslinkable monomer is a polymerizable monomer having only one polymerizable functional group, and a crosslinkable monomer is a polymerizable monomer having two or more polymerizable functional groups that forms crosslinking bonds in a resin through a polymerization reaction. In addition, in the present disclosure, a polymerizable monomer having a solubility of 0.3 g / L or more in distilled water at 20°C is referred to as a hydrophilic monomer, and a polymerizable monomer having a solubility of less than 0.3 g / L in distilled water at 20°C is referred to as a non-hydrophilic monomer.

[0017] 1. Thermal conductivity modifier The thermal conductivity modifier of the present disclosure is a thermal conductivity modifier in the form of hollow particles comprising a resin-containing shell and a hollow portion surrounded by the shell, wherein the shell contains, as the resin, a polymer in which crosslinkable monomer units account for 80 parts by mass or more based on 100 parts by mass of all monomer units, and in an immersion test of the thermal conductivity modifier conducted under an environment of 25°C, in which 0.1 mg of the thermal conductivity modifier is added to 4 mL of acetone, shaken for 10 minutes at a shaking speed of 100 rpm, and then allowed to stand for 48 hours, the proportion of the thermal conductivity modifier that precipitates in acetone is less than 5% by mass.

[0018] The thermal conductivity modifier of the present disclosure has the form of hollow particles comprising a resin-containing shell (outer shell) and a hollow portion surrounded by the shell. In this disclosure, the hollow portion is a cavity-like space clearly distinguishable from the shell of the hollow particle formed from the resin material. The shell of the hollow particle may have a porous structure, in which case the hollow portion is of a size clearly distinguishable from a multitude of minute spaces uniformly dispersed within the porous structure. The hollow portion of a hollow particle can be confirmed, for example, by SEM observation of the particle cross-section, or by TEM observation of the particle itself. In the form of hollow particles of the thermal conductivity modifier disclosed herein, it is preferable that the hollow portion is filled with air or a gas such as nitrogen, or is in a reduced pressure state close to a vacuum.

[0019] Because hollow particles have a hollow portion inside, they can impart properties such as weight reduction and heat insulation to various compositions and molded articles to which they are added. However, conventional heat conductivity modifiers in the form of hollow particles, when added to varnish which is the raw material for molded bodies, tend to collapse as solvents and resins in the varnish penetrate into the inside of the particles. As a result, in molded bodies formed using such varnish, the voids inside the particles cannot be maintained, and the heat conductivity of the molded body cannot be sufficiently reduced. In contrast, the thermal conductivity modifier of this disclosure, although having the form of hollow particles, is resistant to crushing in the varnish and during the molding process of the varnish, and can maintain internal voids in molded articles made from varnish, thereby reducing the thermal conductivity of the molded article. The heat conductivity modifier in the form of hollow particles of the disclosed invention has a polymer contained in the shell that contains 80 parts by mass or more of crosslinkable monomer units per 100 parts by mass of total monomer units. Therefore, it is presumed that the proportion of crosslinkable monomer units in the shell is high, and a dense covalent network is spread throughout the shell. Furthermore, in the immersion test described above, the amount of heat conductivity modifier that precipitates in acetone in the heat conductivity modifier in the form of hollow particles of the disclosed invention is less than 5% by mass. Therefore, it is presumed that the shell has a dense structure that makes it difficult for acetone to penetrate, and the crosslinking structure in the shell is even denser. Thus, the heat conductivity modifier in the form of hollow particles of the disclosed invention has a denser structure than conventional hollow particles that have a shell containing a large amount of crosslinkable monomer units, resulting in improved solvent resistance and strength. Therefore, solvents do not easily penetrate into the inside of the particles, and furthermore, due to its superior strength, it is less likely to be crushed even when added to varnish and the varnish is molded, and the voids inside the particles are maintained in the molded body. Therefore, the thermal conductivity modifier in the form of hollow particles of the present disclosure can be suitably used as a thermal conductivity modifier for molded articles made from varnish. Since the thermal conductivity modifier of this disclosure has the form of hollow particles, the thermal conductivity modifier of this disclosure may be referred to as the hollow particles of this disclosure or simply as hollow particles below.

[0020] The hollow particles of this disclosure preferably have a porosity of 50% or more, more preferably 60% or more, and even more preferably 70% or more. A porosity above the above lower limit results in superior effects such as heat insulation and weight reduction provided by the hollow particles. While there is no particular upper limit to the porosity of the hollow particles of this disclosure, it is preferably 90% or less, more preferably 85% or less, and even more preferably 80% or less, from the viewpoint of suppressing a decrease in the strength of the hollow particles and making them less susceptible to crushing.

[0021] The porosity of the hollow particles in this disclosure is calculated from the apparent density D1 and true density D0 of the hollow particles. The method for measuring the apparent density D1 of hollow particles is as follows. First, a volume of 100 cm³ is used. 3 Approximately 30 cm in a volumetric flask 3Fill the volumetric flask with hollow particles and accurately weigh the mass of the filled hollow particles. Next, carefully fill the volumetric flask filled with hollow particles to the mark with isopropanol, taking care not to introduce air bubbles. Accurately weigh the mass of isopropanol added to the volumetric flask and calculate the apparent density D1 (g / cm³) of the hollow particles based on the following formula (I). 3 Calculate ). Equation (I) Apparent density D1 = [Mass of hollow particles] / (100 - [Mass of isopropanol] ÷ [Specific gravity of isopropanol at measurement temperature]) The apparent density D1 corresponds to the specific gravity of the entire hollow particle, assuming that the hollow portion is considered part of the hollow particle.

[0022] The method for measuring the true density D0 of hollow particles is as follows: After pre-pulverizing the hollow particles, a volume of 100 cm³ is used. 3 Fill a volumetric flask with approximately 10 g of crushed hollow particles and accurately weigh the mass of the crushed particles. Then, add isopropanol to the volumetric flask in the same manner as the apparent density measurement described above, accurately weigh the mass of isopropanol, and calculate the true density D0 (g / cm³) of the hollow particles based on the following formula (II). 3 Calculate ). Formula (II) True density D0 = [Mass of hollow particle fragments] / (100 - [Mass of isopropanol] ÷ [Specific gravity of isopropanol at measurement temperature]) The true density D0 corresponds to the specific gravity of only the shell portion of the hollow particle. As is clear from the measurement method described above, the hollow portion is not considered part of the hollow particle when calculating the true density D0.

[0023] The porosity (%) of a hollow particle is calculated using the following formula (III), given the apparent density D1 and true density D0 of the hollow particle. Formula (III) Porosity (%) = 100 - (Apparent density D1 / True density D0) × 100

[0024] The hollow particles in this disclosure preferably have a volume-average particle size of 1.0 to 30.0 μm. When the volume-average particle size of the hollow particles is greater than or equal to the lower limit, the aggregation of the hollow particles is reduced, resulting in excellent dispersibility. Furthermore, if the volume-average particle size of the hollow particles is greater than or equal to the lower limit, they have a hollow diameter equivalent to half a wavelength of visible light, promoting the reflection and refraction of visible light, thus functioning as a white pigment. Therefore, resin compositions and molded articles containing hollow particles with a volume-average particle size greater than or equal to the lower limit exhibit increased reflectivity. The higher the reflectivity of a resin composition or molded article, the less heat is absorbed from the outside, improving heat resistance; therefore, increasing reflectivity can improve heat resistance. On the other hand, by keeping the volume-average particle size of the hollow particles below the above upper limit, the decrease in the strength of the hollow particles is suppressed, and the thickness of the shell tends to become more uniform. The lower limit of the volume-average particle size of the hollow particles in this disclosure is more preferably 3.0 μm or more, even more preferably 5.0 μm or more, and even more preferably 7.0 μm or more. The upper limit of the volume-average particle size of the hollow particles in this disclosure is more preferably 20.0 μm or less, even more preferably 15.0 μm or less, and even more preferably 10.0 μm or less.

[0025] The particle size distribution (volume-average particle size (Dv) / number-average particle size (Dn)) of the hollow particles may be, for example, between 1.05 and 2.5. A particle size distribution of 2.5 or less allows for particles with less variation in properties such as pressure resistance and heat resistance between particles. Furthermore, a particle size distribution of 2.5 or less enables the production of products with uniform thickness, for example, when manufacturing sheet-like molded articles. The volume-average particle size (Dv) and number-average particle size (Dn) of hollow particles can be determined, for example, by measuring the particle size of the hollow particles using a laser diffraction particle size distribution analyzer, calculating the number average and volume average, respectively, and using the obtained values ​​as the number-average particle size (Dn) and volume-average particle size (Dv) of those particles. The particle size distribution is the value obtained by dividing the volume-average particle size by the number-average particle size.

[0026] The shape of the hollow particles in this disclosure is not particularly limited as long as a hollow portion is formed inside, and examples include spherical, ellipsoidal, and amorphous shapes. Among these, the spherical shape is preferred because it is easy to manufacture and the hollow particles have excellent strength and pressure resistance. Hollow particles may have one or more hollow sections. Furthermore, the shell of the hollow particle, and the partition walls separating adjacent hollow sections if there are two or more, may be porous. In order to maintain a good balance between the high porosity of the hollow particle and its mechanical strength, it is preferable that the particle has only one hollow section inside. The hollow particles may have an average circularity of 0.950 to 0.995. One example of the shape of a hollow particle is a bag consisting of a thin film and inflated with gas, the cross-section of which is shown as hollow particle 100 in Figure 1(5) below. In this example, a thin film is provided on the outside, and the inside is filled with gas. The particle shape can be confirmed, for example, by SEM or TEM. Furthermore, the internal shape of the particle can be confirmed by SEM or TEM after the particle has been sliced ​​crosswise using a known method.

[0027] The hollow particles of this disclosure contain a polymer as the resin in the shell, which contains 80 parts by mass or more of crosslinkable monomer units per 100 parts by mass of total monomer units. The polymer forms the framework of the shell of the hollow particles, and by containing crosslinkable monomer units in the above proportion, the shell of the hollow particles of this disclosure has a densely interwoven covalent network. In the above polymer, the content of crosslinkable monomer units in 100 parts by mass of total monomer units is preferably 85 parts by mass or more, more preferably 90 parts by mass or more, from the standpoint of improving the strength and solvent resistance of the hollow particles and improving the effects of heat insulation and weight reduction by the hollow particles. The upper limit of the content of the above crosslinkable monomer units is not particularly limited and may be 100 parts by mass or less, but from the standpoint of sufficiently containing hydrophilic non-crosslinkable monomer units described later, it is preferably 98 parts by mass or less, more preferably 97 parts by mass or less. In this disclosure, the crosslinkable monomer unit is a monomer unit derived from a crosslinkable monomer, and in the polymer described above, if the content of the crosslinkable monomer unit is less than 100 parts by mass, the monomer units other than the crosslinkable monomer unit are non-crosslinkable monomer units derived from a non-crosslinkable monomer. The polymer described above is typically a polymer of a first polymerizable monomer and a second polymerizable monomer obtained by a first polymerization reaction and a second polymerization reaction in the method for producing hollow particles of the present disclosure described later. That is, in the hollow particles of the present disclosure, the crosslinkable monomer units and non-crosslinkable monomer units contained in the polymer described above are usually derived from the first polymerizable monomer and the second polymerizable monomer described later. The specific details of the crosslinkable and non-crosslinkable monomers used in the synthesis of the above polymer are as described in the method for producing hollow particles in this disclosure, which will be discussed later.

[0028] The above polymer contains at least one crosslinkable monomer unit selected from a difunctional crosslinkable monomer derived from a difunctional crosslinkable monomer, and a trifunctional or higher crosslinkable monomer unit derived from a trifunctional or higher crosslinkable monomer. In particular, it is preferable to include at least a difunctional crosslinkable monomer unit in order to improve the strength and solvent resistance of the hollow particles and to improve the effects of heat insulation and weight reduction by the hollow particles, and it is even more preferable to include a combination of a difunctional crosslinkable monomer unit and a trifunctional or higher crosslinkable monomer unit in order to further improve the strength of the hollow particles. In this disclosure, crosslinkable monomer units derived from a bifunctional crosslinkable monomer may be referred to as "bifunctional crosslinkable monomer units," and crosslinkable monomer units derived from a trifunctional or more crosslinkable monomer may be referred to as "trifunctional or more crosslinkable monomer units."

[0029] When the above polymer contains bifunctional crosslinkable monomer units, the content of bifunctional crosslinkable monomer units in 100 parts by mass of the total monomer units of the above polymer is not particularly limited, but the lower limit is preferably 65 parts by mass or more, more preferably 70 parts by mass or more, and even more preferably 75 parts by mass or more, from the standpoint of improving the strength and solvent resistance of the hollow particles and improving the effects of heat insulation and weight reduction by the hollow particles. On the other hand, the upper limit may be 100 parts by mass or less, but from the standpoint of sufficiently containing trifunctional or more crosslinkable monomer units or hydrophilic non-crosslinkable monomer units described later, it is preferably 98 parts by mass or less, more preferably 95 parts by mass or less, and even more preferably 90 parts by mass or less.

[0030] When the above polymer contains three or more crosslinkable monomer units, the content of three or more crosslinkable monomer units in 100 parts by mass of the total monomer units of the above polymer is not particularly limited, but the lower limit is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more, from the standpoint of improving the strength and solvent resistance of the hollow particles and improving the effects of heat insulation and weight reduction by the hollow particles. On the other hand, the upper limit is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, and even more preferably 30 parts by mass or less, and even more preferably 25 parts by mass or less, from the standpoint of sufficiently containing two or more crosslinkable monomer units or hydrophilic non-crosslinkable monomer units described later.

[0031] Furthermore, the crosslinkable monomer units contained in the above polymer may also include crosslinkable monomer units derived from (meth)acrylic crosslinkable monomers having a (meth)acryloyl group as a polymerizable functional group. This makes it possible to produce hollow particles with excellent strength and heat resistance. When the polymer contains crosslinkable monomer units derived from a (meth)acrylic crosslinkable monomer, the content of the crosslinkable monomer units derived from the (meth)acrylic crosslinkable monomer is preferably 50 parts by mass or more, more preferably 70 parts by mass or more, and even more preferably 90 parts by mass or more, per 100 parts by mass of crosslinkable monomer units, and the crosslinkable monomer units may consist of (meth)acrylic crosslinkable monomer units. The specific details of the (meth)acrylic crosslinkable monomer will be described later in the manufacturing method of the thermal conductivity modifier in this disclosure.

[0032] Furthermore, the polymer preferably further contains non-crosslinkable monomer units, more preferably hydrophilic non-crosslinkable monomer units having a solubility of 0.3 g / L or more in distilled water at 20°C, and particularly preferably contains hydrophilic non-crosslinkable monomer units derived from a second polymerizable monomer described later. By including a combination of crosslinkable and non-crosslinkable monomer units in the polymer, the mechanical properties of the hollow particle shell are improved. In particular, by including hydrophilic non-crosslinkable monomer units as non-crosslinkable monomer units, the shell tends to have a dense structure, which improves the strength and solvent resistance of the hollow particles, thereby improving the effects of heat insulation and weight reduction provided by the hollow particles. In the above polymer, the content of non-crosslinkable monomer units in 100 parts by mass of total monomer units is 0 to 20 parts by mass. From the viewpoint of improving the strength of hollow particles, the lower limit is preferably 2 parts by mass or more, more preferably 3 parts by mass or more, and even more preferably 4 parts by mass or more, and the upper limit is preferably 15 parts by mass or less, more preferably 12 parts by mass or less, and even more preferably 10 parts by mass or less. In the above polymer, the content of hydrophilic non-crosslinked monomer units in 100 parts by mass of total monomer units is preferably 2 parts by mass or more, more preferably 3 parts by mass or more, and even more preferably 4 parts by mass or more, from the standpoint of improving the strength and solvent resistance of the hollow particles and improving the effects of heat insulation and weight reduction by the hollow particles, as a lower limit, preferably 20 parts by mass or less, more preferably 15 parts by mass or less, even more preferably 12 parts by mass or less, and even more preferably 10 parts by mass or less.

[0033] In the hollow particles of this disclosure, the content of the polymer is preferably 90% by mass or more, more preferably 95% by mass or more, of 100% by mass of the total solids content of the shell. By setting the content of the polymer to above the lower limit, the strength of the hollow particles can be improved.

[0034] In the hollow particles disclosed herein, in an immersion test in which 0.1 mg of hollow particles is added to 4 mL of acetone at 25°C, shaken at a shaking speed of 100 rpm for 10 minutes, and then allowed to stand for 48 hours, less than 5% by mass of hollow particles precipitates in the acetone. The percentage of hollow particles that precipitate in the acetone in the above immersion test serves as an indicator of the density of the hollow particle shell, and the lower the percentage of hollow particles that precipitate in the acetone in the above immersion test, the denser the hollow particle shell is presumed to be. In order to ensure that the amount of hollow particles that precipitate in acetone in the above immersion test is less than 5% by mass, for example, as in the method for producing hollow particles in the present disclosure described later, hollow particles can be produced by adding a second polymerizable monomer, which is a hydrophilic monomer, when the polymerization conversion rate of a first polymerizable monomer containing a specific amount or more of crosslinkable monomers reaches 93% by mass or more in the step of subjecting the suspension to a polymerization reaction, and further subjecting it to a polymerization reaction, such that the content ratio of crosslinkable monomer units in the polymer that forms the shell is 80% by mass or more.

[0035] Furthermore, in SEM observation, it is preferable that the hollow particles in this disclosure have 5 or fewer hollow particles with interconnecting holes or shell defects out of 100 hollow particles. Generally, hollow particles can be classified into two types: those in which the shell does not have connecting holes between the hollow portion and the external space of the particle, and those in which the shell has one or more connecting holes, allowing the hollow portion to connect to the outside of the particle through these holes. Depending on the size of the hollow particle, the diameter of the connecting holes is usually around 10 to 500 nm. While connecting holes can sometimes impart beneficial functions to hollow particles, they can also reduce the strength of the hollow particle and make it more prone to collapse because they represent areas where the shell is missing. Furthermore, hollow particles may have extremely large crack-like shell defects relative to their particle size. Depending on the size of the hollow particle, cracks with a length of 1 μm or more generally significantly degrade the strength of the hollow particle and are therefore recognized as shell defects. In the immersion test of hollow particles described above, if the amount of hollow particles that precipitate in acetone is less than 5% by mass, it can be considered that there are 5 or fewer hollow particles with interconnecting pores or shell defects out of 100 hollow particles. However, even if the shell does not have interconnecting pores or shell defects, the amount of hollow particles that precipitate in the immersion test described above may be 5% by mass or more. Therefore, in the immersion test of hollow particles described above, if the amount of precipitated hollow particles is less than 5% by mass, it is considered to indicate that the shell has very few interconnecting pores and shell defects, and that the shell has a dense cross-linking structure.

[0036] 2. Method for manufacturing thermal conductivity modifier Examples of thermal conductivity modifiers in the form of hollow particles in this disclosure include, for example, A step of preparing a mixture containing a first polymerizable monomer including a crosslinkable monomer, a hydrocarbon solvent, a dispersion stabilizer, and an aqueous medium, The steps include: preparing a suspension in which droplets of the monomer composition containing the first polymerizable monomer and the hydrocarbon solvent are dispersed in the aqueous medium by suspending the aforementioned mixture; The step includes subjecting the suspension to a polymerization reaction, These hollow particles can be obtained by a method for producing hollow particles, in which, in the step of subjecting the suspension to a polymerization reaction, when the polymerization conversion rate of the first polymerizable monomer reaches 93% by mass or more, a second polymerizable monomer having a solubility of 0.3 g / L or more in distilled water at 20°C is added and the polymerization reaction is further carried out.

[0037] The above method for producing hollow particles follows a basic technique in which a mixture containing a first polymerizable monomer, a hydrocarbon solvent, a dispersion stabilizer, and an aqueous medium is suspended, causing the first polymerizable monomer and the hydrocarbon solvent to undergo phase separation, resulting in a suspension in which droplets having a distribution structure in which the first polymerizable monomer is concentrated on the surface and the hydrocarbon solvent is concentrated in the center are dispersed in the aqueous medium, and this suspension is subjected to a polymerization reaction to harden the surface of the droplets and form hollow particles having a hollow portion filled with the hydrocarbon solvent. In this basic technology, when the polymerization conversion rate of the first polymerizable monomer containing a crosslinkable monomer reaches 93% by mass or more in the step of subjecting the suspension to polymerization, a second polymerizable monomer, which is a hydrophilic monomer whose solubility in distilled water at 20°C is 93% by mass or more, is added and subjected to further polymerization, thereby enabling the production of hollow particles in which less than 5% by mass of hollow particles precipitate in acetone in the above-mentioned immersion test of hollow particles. When a crosslinkable monomer is used as the polymerizable monomer for forming the shell of the hollow particles, unreacted polymerizable functional groups tend to remain in the shell. The more unreacted polymerizable functional groups that remain, the coarser the crosslinked structure of the shell becomes. Therefore, in hollow particles obtained by conventional manufacturing methods, it is thought that 5% or more by mass of hollow particles precipitate in acetone in the above-mentioned immersion test of hollow particles due to the remaining unreacted polymerizable functional groups. In the above method for producing hollow particles, a suspension in which droplets of a monomer composition containing a first polymerizable monomer containing a large amount of crosslinkable monomers are dispersed in an aqueous medium is subjected to a polymerization reaction. The first polymerization reaction is carried out until the polymerization conversion rate of the first polymerizable monomer reaches 93% by mass or more. Then, a second polymerizable monomer, which is a hydrophilic monomer, is added and a second polymerization reaction is carried out further. It is believed that this can improve the overall reaction rate of the polymerizable monomer, including the first and second polymerizable monomers. In this disclosure, particles having a shell containing a polymer of the first polymerizable monomer and a hollow portion filled with a hydrocarbon solvent, obtained by the first polymerization reaction described above, may be referred to as first precursor particles, and compositions containing these first precursor particles may be referred to as first precursor compositions. Furthermore, particles having a shell containing polymers of the first polymerizable monomer and the second polymerizable monomer and a hollow portion filled with a hydrocarbon solvent, obtained by the second polymerization reaction described above, may be considered intermediates of hollow particles with a hollow portion filled with gas, and may be referred to as second precursor particles, and compositions containing these second precursor particles may be referred to as second precursor compositions. In the above method for producing hollow particles, the second polymerizable monomer has a solubility in distilled water at 20°C that is greater than or equal to the specified value, so when added to the first precursor composition, it is easily incorporated into the shell of the first precursor particles. The second polymerizable monomer, being a hydrophilic monomer, has affinity for both the first polymerizable monomer and the aqueous medium. Therefore, when added to the first precursor composition, it is thought to be incorporated into the shell formed by the first polymerizable monomer, thereby promoting the thermal motion of the shell. During the second polymerization reaction, the polymerization reaction proceeds with the second polymerizable monomer incorporated into the shell formed by the first polymerizable monomer, while the thermal motion of the shell is promoted. As a result, the reaction rate is high, and the polymerization reaction of the second polymerizable monomer incorporated into the shell and the polymerizable functional groups of the first polymerizable monomer that remained unreacted proceeds sufficiently, resulting in a dense crosslinking structure. It is therefore estimated that a shell is formed that is resistant to acetone penetration.

[0038] The above method for producing hollow particles includes the steps of preparing a mixture, preparing a suspension, and subjecting the suspension to a polymerization reaction, and may also include other steps. Furthermore, to the extent that it is technically possible, two or more of the above steps and other additional steps may be performed simultaneously as a single step, or in any order. For example, the preparation of the mixture and the suspension may be performed simultaneously in a single process, such as adding the materials for preparing the mixture while simultaneously performing the suspension.

[0039] A preferred example of a method for producing the above-mentioned hollow particles is a manufacturing method that includes the following steps. (1) Mixed liquid preparation process A process for preparing a mixture containing a first polymerizable monomer, a hydrocarbon solvent, a dispersion stabilizer, and an aqueous medium. (2) Suspension process A step of preparing a suspension in which droplets of a monomer composition containing a first polymerizable monomer and a hydrocarbon solvent are dispersed in an aqueous medium by suspending the aforementioned mixture. (3) Polymerization process (3-1) First polymerization step A first polymerization reaction is performed in which the suspension is subjected to a polymerization reaction until the polymerization conversion rate of the first polymerizable monomer reaches 93% by mass or more, thereby preparing a first precursor composition comprising a shell containing a polymer of the first polymerizable monomer and first precursor particles having a hollow portion filled with a hydrocarbon solvent. (3-2) Second polymerization step A second precursor composition is prepared by adding a second polymerizable monomer having a solubility of 0.3 g / L or more in distilled water at 20°C to the first precursor composition and carrying out a second polymerization reaction, thereby preparing a second precursor composition containing a shell containing polymers of the first polymerizable monomer and the second polymerizable monomer, and second precursor particles having a hollow portion filled with a hydrocarbon solvent. (4) Solid-liquid separation process A step of obtaining second precursor particles containing a hydrocarbon solvent in a hollow portion by performing solid-liquid separation of the second precursor composition, and (5) Solvent removal process A step of removing the hydrocarbon solvent contained within the second precursor particles obtained by the solid-liquid separation step to obtain hollow particles.

[0040] Figure 1 is a schematic diagram illustrating an example of the above manufacturing method. (1) to (5) in Figure 1 correspond to each of the above steps (1) to (5). The white arrows between the figures indicate the order of each step. Note that Figure 1 is merely a schematic diagram for illustrative purposes, and the above manufacturing method is not limited to that shown in the figure. Furthermore, the structure, dimensions, and shape of the materials used in the manufacturing method of this disclosure are not limited to the structure, dimensions, and shape of the various materials shown in these figures. Figure 1(1) is a schematic cross-sectional view showing one embodiment of the mixture in the mixture preparation process. As shown in this figure, the mixture includes an aqueous medium 1 and a low-polarity material 2 dispersed in the aqueous medium 1. Here, the low-polarity material 2 means a material that has low polarity and does not easily mix with the aqueous medium 1. In this disclosure, the low-polarity material 2 includes a first polymerizable monomer and a hydrocarbon solvent. Figure 1(2) is a schematic cross-sectional view showing one embodiment of a suspension in the suspension process. The suspension comprises an aqueous medium 1 and droplets 10 of a monomer composition dispersed in the aqueous medium 1. The droplets 10 of the monomer composition contain a first polymerizable monomer and a hydrocarbon solvent, but the distribution within the droplets is not uniform. The droplets 10 of the monomer composition have a structure in which the hydrocarbon solvent 4a and a material 4b other than the hydrocarbon solvent containing the first polymerizable monomer are phase-separated, with the hydrocarbon solvent 4a unevenly distributed in the center and the material 4b other than the hydrocarbon solvent unevenly distributed on the surface side, and a dispersion stabilizer (not shown) attached to the surface. Figure 1(3) is a schematic cross-sectional view showing one embodiment of a composition (second precursor composition) that includes hollow particles (second precursor particles) containing a hydrocarbon solvent in their hollow portions, obtained by a polymerization process. The composition includes an aqueous medium 1 and hollow particles (second precursor particles) 20 dispersed in the aqueous medium 1, each containing a hydrocarbon solvent 4a in its hollow portion. The shell 6 forming the outer surface of the second precursor particles 20 is formed by the polymerization of the first polymerizable monomer in a droplet 10 of the monomer composition, and the polymerization of a second polymerizable monomer added later. Figure 1(4) is a schematic cross-sectional view showing one embodiment of hollow particles (second precursor particles) containing a hydrocarbon solvent in the hollow portion after the solid-liquid separation process. Figure 1(4) shows the state after the aqueous medium 1 has been removed from the state shown in Figure 1(3). Figure 1(5) is a schematic cross-sectional view showing one embodiment of hollow particles after the solvent removal process. Figure 1(5) shows the state after the hydrocarbon solvent 4a has been removed from the state shown in Figure 1(4). By removing the hydrocarbon solvent from the hollow particles (second precursor particles) that contain the hydrocarbon solvent in the hollow portion, hollow particles 100 are obtained that have a gas-filled hollow portion 8 inside the shell 6. The following describes the five processes mentioned above, as well as other processes, in order.

[0041] (1) Mixed liquid preparation process This process involves preparing a mixture containing a first polymerizable monomer, a hydrocarbon solvent, a dispersion stabilizer, and an aqueous medium. The mixture preferably contains an oil-soluble polymerization initiator as a polymerization initiator. Furthermore, the mixture may contain other materials, such as suspension stabilizers, to the extent that they do not impair the effects of the present disclosure. The materials of the mixture will be described in the following order: (A) the first polymerizable monomer, (B) the oil-soluble polymerization initiator, (C) the hydrocarbon solvent, (D) the dispersion stabilizer, and (E) the aqueous medium.

[0042] (A) First polymerizable monomer The first polymerizable monomer comprises at least a crosslinkable monomer and may further comprise non-crosslinkable monomers to the extent that it does not impair the effects of the present disclosure. As the first polymerizable monomer, a (meth)acrylic polymerizable monomer having a (meth)acryloyl group as the polymerizable functional group is preferably used because the polymerization reaction is easily stabilized and hollow particles with high heat resistance can be obtained.

[0043] [Cross-linkable monomers] Because crosslinkable monomers have multiple polymerizable functional groups, they can be linked together, thereby increasing the crosslinking density of the shell. Examples of crosslinkable monomers include divinylbenzene, divinyldiphenyl, divinylnaphthalene, diallylphthalate, diallylamine, allyl(meth)acrylate, vinyl(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, tricyclodecanedimethanol di(meth)acrylate, 2-hydroxy-3-(meth)acrylpropyl(meth)acrylate, etc. Examples include difunctional crosslinkable monomers having two polymerizable functional groups; trifunctional or more crosslinkable monomers having three or more polymerizable functional groups, such as trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol poly(meth)acrylate, and their ethoxylated derivatives. These crosslinkable monomers can be used individually or in combination of two or more. Among these crosslinkable monomers, hydrophilic crosslinkable monomers with a solubility of 0.3 g / L or more in distilled water at 20°C include, for example, ethylene glycol dimethacrylate, diethylene glycol diacrylate, allyl methacrylate, vinyl methacrylate, 2-hydroxy-3-methacrylatelpropyl acrylate, diallylamine, and the like. The crosslinkable monomer contained in the first polymerizable monomer may be a hydrophilic crosslinkable monomer with a solubility of 0.3 g / L or more in distilled water at 20°C, or a non-hydrophilic crosslinkable monomer with a solubility of less than 0.3 g / L, and is not particularly limited.

[0044] The first polymerizable monomer includes at least one crosslinkable monomer selected from a bifunctional crosslinkable monomer and a trifunctional or more crosslinkable monomer. In particular, it is more preferable to include a combination of a bifunctional crosslinkable monomer and a trifunctional or more crosslinkable monomer from the standpoint of improving the strength and solvent resistance of the hollow particles and improving the effects of heat insulation and weight reduction by the hollow particles. When the first polymerizable monomer includes a trifunctional or more crosslinkable monomer, it is advantageous in that a denser covalent network can be formed in the shell, but there is a tendency for unreacted polymerizable functional groups to remain after the first polymerization reaction. In the above manufacturing method, even when the first polymerizable monomer includes a trifunctional or more crosslinkable monomer, by adding a hydrophilic monomer as the second polymerizable monomer and carrying out a second polymerization reaction, the polymerization reaction of the unreacted polymerizable functional groups remaining after the first polymerization reaction can proceed more easily. Therefore, by including a trifunctional or crosslinkable monomer in the first polymerizable monomer, the crosslinked structure of the shell is made denser, improving the strength and solvent resistance of the hollow particles, thereby enhancing the effects of heat insulation and weight reduction provided by the hollow particles.

[0045] Furthermore, as the crosslinkable monomer included in the first polymerizable monomer, a (meth)acrylic crosslinkable monomer having a (meth)acryloyl group as a polymerizable functional group is preferred because the polymerization reaction is easily stabilized and hollow particles with excellent strength and heat resistance can be obtained. In other words, as the bifunctional crosslinkable monomer used in the first polymerizable monomer, bifunctional (meth)acrylic crosslinkable monomers such as allyl (meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, and pentaerythritol di(meth)acrylate are preferred, and among these, ethylene glycol di(meth)acrylate and pentaerythritol di(meth)acrylate are more preferred. The crosslinkable monomer with three or more functions used in the first polymerizable monomer is preferably a (meth)acrylic crosslinkable monomer with three or more functions, such as trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol poly(meth)acrylate, and ethoxylated derivatives thereof. However, pentaerythritol tetra(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, and dipentaerythritol poly(meth)acrylate are more preferred, and trimethylolpropane tri(meth)acrylate and pentaerythritol tetra(meth)acrylate are even more preferred. In this disclosure, the (meth)acrylic crosslinkable monomer may be any crosslinkable monomer having at least one (meth)acryloyl group as a polymerizable functional group, but it is preferable that all polymerizable functional groups are (meth)acryloyl groups.

[0046] When the first polymerizable monomer contains a (meth)acrylic crosslinkable monomer, the content of the (meth)acrylic crosslinkable monomer is preferably 50 parts by mass or more, more preferably 70 parts by mass or more, and even more preferably 90 parts by mass or more, in 100 parts by mass of the crosslinkable monomer contained in the first polymerizable monomer, and the crosslinkable monomer contained in the first polymerizable monomer may consist of a (meth)acrylic crosslinkable monomer.

[0047] In 100 parts by mass of the first polymerizable monomer, the content of the crosslinkable monomer is preferably 85 to 100 parts by mass, more preferably 90 to 100 parts by mass, and even more preferably 95 to 100 parts by mass. By having a crosslinkable monomer content equal to or greater than the above lower limit, the polymer contained in the formed shell tends to be a polymer containing 80 to 100 parts by mass of crosslinkable monomer units per 100 parts by mass of total monomer units. Furthermore, because the proportion of crosslinkable monomer units in the shell of the hollow particles is sufficiently high, a dense covalent network is formed within the shell, resulting in improved strength and solvent resistance of the hollow particles, and consequently, improved effects such as heat insulation and weight reduction by the hollow particles.

[0048] When the first polymerizable monomer contains a bifunctional crosslinkable monomer as a crosslinkable monomer, the content of the bifunctional crosslinkable monomer in 100 parts by mass of the first polymerizable monomer is not particularly limited, but the lower limit is 70 parts by mass or more, more preferably 80 parts by mass or more, in order to improve the strength and solvent resistance of the hollow particles and to improve the effects of heat insulation and weight reduction by the hollow particles, while the upper limit may be 100 parts by mass or less, but in order to sufficiently contain trifunctional or more crosslinkable monomer units, it is preferably 95 parts by mass or less, more preferably 90 parts by mass or less.

[0049] When the first polymerizable monomer contains a crosslinkable monomer with three or more functions, the content of the crosslinkable monomer with three or more functions in 100 parts by mass of the first polymerizable monomer is not particularly limited, but the lower limit is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more, from the standpoint of improving the strength and solvent resistance of the hollow particles and improving the effects of heat insulation and weight reduction by the hollow particles, the upper limit is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, and even more preferably 30 parts by mass or less, and even more preferably 25 parts by mass or less, from the standpoint of sufficiently containing a crosslinkable monomer with two or more functions.

[0050] [Non-crosslinkable monomers] The first polymerizable monomer may further contain a non-crosslinkable monomer. As non-crosslinkable monomers, monovinyl monomers are preferably used. A monovinyl monomer is a compound having one polymerizable vinyl functional group. Examples of monovinyl monomers include (meth)acrylate alkyl esters having alkyl groups with 6 or more carbon atoms, such as 2-ethylhexyl (meth)acrylate and lauryl (meth)acrylate; aromatic vinyl monomers such as styrene, vinyltoluene, α-methylstyrene, p-methylstyrene, and halogenated styrene; monoolefin monomers such as ethylene, propylene, and butylene; diene monomers such as butadiene and isoprene; vinyl carboxylate monomers such as vinyl acetate; halogenated vinyl monomers such as vinyl chloride; and halogenated vinyl monomers such as vinylidene chloride. Examples include non-hydrophilic, non-crosslinkable monomers such as vinylidene genate monomers and vinylpyridine monomers, and hydrophilic, non-crosslinkable monomers such as alkyl (meth)acrylates having C1-C5 alkyl groups such as methyl (meth)acrylate, ethyl (meth)acrylate, and butyl (meth)acrylate; (meth)acrylamides and their derivatives such as (meth)acrylamide, N-methylol(meth)acrylamide, and N-butoxymethyl(meth)acrylamide; nitrile (meth)acrylates and their derivatives; and non-crosslinkable monomers containing polar groups. Examples of non-crosslinkable monomers containing polar groups include, for example, non-crosslinkable monomers containing polar groups selected from carboxyl groups, hydroxyl groups, sulfonic acid groups, amino groups, polyoxyethylene groups, and epoxy groups. More specifically, examples include carboxyl group-containing monomers such as ethylenically unsaturated carboxylic acid monomers like (meth)acrylic acid, crotonic acid, cinnamic acid, itaconic acid, fumaric acid, maleic acid, and butentricarboxylic acid; hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; sulfonic acid group-containing monomers such as styrene sulfonic acid; amino group-containing monomers such as dimethylaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate; polyoxyethylene group-containing monomers such as methoxypolyethylene glycol (meth)acrylate; and epoxy group-containing monomers such as glycidyl (meth)acrylate, allyl glycidyl ether, and 4-hydroxybutyl acrylate glycidyl ether. These non-crosslinkable monomers can be used individually or in combination of two or more types. As the non-crosslinkable monomer used as the first polymerizable monomer, hydrophilic non-crosslinkable monomers are preferred in terms of improving the strength of the hollow particles, alkyl (meth)acrylates having an alkyl group with 1 to 5 carbon atoms are more preferred, and alkyl (meth)acrylates having an alkyl group with 1 to 4 carbon atoms are even more preferred.

[0051] In the first polymerizable monomer, polymerizable monomers other than the crosslinkable monomer are non-crosslinkable monomers. The content of non-crosslinkable monomers in the first polymerizable monomer is preferably 0 to 15 parts by mass per 100 parts by mass of the first polymerizable monomer. In order to suppress the decrease in reactivity of the first polymerizable monomer, improve the strength and solvent resistance of the hollow particles, and improve the effects of heat insulation and weight reduction by the hollow particles, the content of non-crosslinkable monomers per 100 parts by mass of the first polymerizable monomer is more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less. It is particularly preferable that the first polymerizable monomer does not contain non-crosslinkable monomers.

[0052] The content of the first polymerizable monomer in the mixture is not particularly limited, but from the viewpoint of balancing the porosity, particle size, and mechanical strength of the hollow particles, it is usually 15 to 55% by mass, more preferably 25 to 40% by mass, based on 100% by mass of the total mass of the components in the mixture excluding the aqueous medium.

[0053] Furthermore, from the viewpoint of improving the mechanical strength of the hollow particles, the content of the first polymerizable monomer relative to 100% by mass of the total solid content of the material that becomes the oil phase in the mixed liquid, excluding the hydrocarbon solvent, is preferably 90% by mass or more, more preferably 95% by mass or more.

[0054] (B) Oil-soluble polymerization initiator In this disclosure, it is preferable that the mixture contains an oil-soluble polymerization initiator as a polymerization initiator. As a method for polymerizing droplets of monomer composition after suspending the mixture, there is an emulsion polymerization method using a water-soluble polymerization initiator and a suspension polymerization method using an oil-soluble polymerization initiator, and suspension polymerization can be performed by using an oil-soluble polymerization initiator. The oil-soluble polymerization initiator is not particularly limited as long as it is lipophilic and has a solubility in water of 0.2% by mass or less. Examples of oil-soluble polymerization initiators include benzoyl peroxide, lauroyl peroxide, t-butyl peroxide-2-ethylhexanoate, 2,2'-azobis(2,4-dimethylvaleronitrile), and azobisisobutyronitrile. When the total mass of the first polymerizable monomer in the mixture is 100 parts by mass, the content of the oil-soluble polymerization initiator is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 7 parts by mass, and even more preferably 1 to 5 parts by mass. By having an oil-soluble polymerization initiator content of 0.1 to 10 parts by mass, the polymerization reaction proceeds sufficiently, and there is little risk of residual oil-soluble polymerization initiator after the polymerization reaction is completed, and the risk of unexpected side reactions is also small.

[0055] (C) Hydrocarbon solvents In this disclosure, a hydrocarbon solvent is used as a non-polymerizable and poorly water-soluble organic solvent. The hydrocarbon solvent acts as a spacer material that forms hollow spaces inside the particles. In the suspension step described later, a suspension is obtained in which droplets of the monomer composition containing the hydrocarbon solvent are dispersed in an aqueous medium. In the suspension step, phase separation occurs within the droplets of the monomer composition, resulting in the less polar hydrocarbon solvent tending to accumulate inside the droplets. Finally, in the droplets of the monomer composition, the hydrocarbon solvent is distributed inside, and other materials other than the hydrocarbon solvent are distributed around its periphery according to their respective polarities. Then, in the polymerization process described later, an aqueous dispersion containing hollow particles encapsulating a hydrocarbon solvent is obtained. That is, as the hydrocarbon solvent accumulates inside the particles, a hollow space filled with the hydrocarbon solvent is formed inside the resulting precursor particles.

[0056] The type of hydrocarbon solvent is not particularly limited. Examples of hydrocarbon solvents include saturated hydrocarbon solvents such as butane, pentane, n-hexane, cyclohexane, heptane, and octane; aromatic hydrocarbon solvents such as benzene, toluene, and xylene; and relatively volatile solvents such as carbon disulfide and carbon tetrachloride. The porosity of the hollow particles can be adjusted by changing the amount of hydrocarbon solvent in the mixture. In the suspension step described later, the polymerization reaction proceeds with oil droplets containing crosslinkable monomers, etc., encapsulating the hydrocarbon solvent. Therefore, the higher the hydrocarbon solvent content, the higher the porosity of the resulting hollow particles tends to be. Preferably, the hydrocarbon solvent contains 50% by mass or more of saturated hydrocarbon solvent in a total amount of 100% by mass of hydrocarbon solvents. This allows for sufficient phase separation within droplets of polymerizable monomer liquid, making it easier to obtain hollow particles with only one hollow portion and suppressing the formation of porous particles. The proportion of saturated hydrocarbon solvent is preferably 60% by mass or more, and more preferably 80% by mass or more, from the standpoint of further suppressing the formation of porous particles and ensuring that the hollow portions of each hollow particle are uniform. Furthermore, hydrocarbon solvents having 4 to 7 carbon atoms are preferred. Hydrocarbon compounds having 4 to 7 carbon atoms are easily encapsulated in the first precursor particles during the polymerization process and can be easily removed from the second precursor particles during the solvent removal process. Among these, hydrocarbon solvents having 5 or 6 carbon atoms are particularly preferred. Furthermore, although not particularly limited, hydrocarbon solvents are preferred to have a boiling point of 130°C or lower, and more preferably 100°C or lower, as they are easily removed in the solvent removal process described later. Also, hydrocarbon solvents are preferred to have a boiling point of 50°C or higher, and more preferably 60°C or higher, as they are easily encapsulated in the first precursor particles.

[0057] Furthermore, the hydrocarbon solvent preferably has a relative permittivity of 3 or less at 20°C. Relative permittivity is one indicator of the polarity of a compound. When the relative permittivity of the hydrocarbon solvent is sufficiently small, such as 3 or less, it is thought that phase separation proceeds rapidly in the droplets of the monomer composition, and hollow spaces are easily formed. Examples of solvents with a relative permittivity of 3 or less at 20°C are as follows. (The value in parentheses is the relative permittivity.) Heptane (1.9), n-hexane (1.9), cyclohexane (2.0), benzene (2.3), toluene (2.4). Regarding the relative permittivity at 20°C, values ​​can be found in publicly available literature (for example, "Basic Chemical Handbook," edited by the Chemical Society of Japan, 4th revised edition, Maruzen Co., Ltd., published September 30, 1993, pp. II-498 to II-503), as well as other technical information. Methods for measuring the relative permittivity at 20°C include, for example, relative permittivity tests conducted in accordance with JISC 2101:1999, item 23, with the measurement temperature set at 20°C.

[0058] In this disclosure, the content of the hydrocarbon solvent in the mixture is preferably 50 parts by mass or more and 500 parts by mass or less per 100 parts by mass of the total mass of the first polymerizable monomer, as this makes it easier to control the particle size of the hollow particles, easier to increase the porosity while maintaining the strength of the hollow particles, and easier to reduce the amount of residual hydrocarbon solvent in the particles. The content of the hydrocarbon solvent in the mixture is more preferably 60 parts by mass or more and 400 parts by mass or less, even more preferably 70 parts by mass or more and 300 parts by mass or less, and even more preferably 80 parts by mass or more and 200 parts by mass or less per 100 parts by mass of the total mass of the first polymerizable monomer.

[0059] (D) Dispersion stabilizer A dispersion stabilizer is an agent used in the suspension process to disperse droplets of a monomer composition in an aqueous medium. In this disclosure, it is preferable to use an inorganic dispersion stabilizer as the dispersion stabilizer because it allows for easy control of the particle size of the droplets in the suspension, narrows the particle size distribution of the resulting hollow particles, and suppresses a decrease in the strength of the hollow particles by preventing the shell from becoming too thin. Examples of inorganic dispersion stabilizers include sulfates such as barium sulfate and calcium sulfate; carbonates such as barium carbonate, calcium carbonate, and magnesium carbonate; phosphates such as calcium phosphate; metal oxides such as aluminum oxide and titanium oxide; and metal hydroxides such as aluminum hydroxide, magnesium hydroxide, calcium hydroxide, barium hydroxide, and ferric hydroxide. These inorganic dispersion stabilizers can be used individually or in combination of two or more. Among the inorganic dispersion stabilizers mentioned above, poorly water-soluble inorganic metal salts such as sulfates, carbonates, phosphates, and metal hydroxides are preferred, metal hydroxides are more preferred, and magnesium hydroxide is particularly preferred. In this disclosure, the poorly water-soluble inorganic metal salt is preferably an inorganic metal salt whose solubility in 100 g of water is 0.5 g or less. In this disclosure, it is particularly preferable to use a poorly water-soluble inorganic dispersion stabilizer in the form of colloidal particles dispersed in an aqueous medium, that is, in the form of a colloidal dispersion containing poorly water-soluble inorganic dispersion stabilizer colloidal particles. This allows for a narrower particle size distribution of the monomer composition droplets, and also makes it easy to keep the amount of residual inorganic dispersion stabilizer in the resulting hollow particles low after washing. A colloidal dispersion containing poorly water-soluble inorganic dispersion stabilizer colloid particles can be prepared, for example, by reacting at least one selected from alkali metal hydroxides and alkaline earth metal hydroxides with a water-soluble polyvalent metal salt (excluding alkaline earth metal hydroxides) in an aqueous medium. Examples of alkali metal hydroxides include lithium hydroxide, sodium hydroxide, and potassium hydroxide. Examples of alkaline earth metal hydroxides include barium hydroxide and calcium hydroxide. The water-soluble polyvalent metal salt can be any water-soluble polyvalent metal salt other than the alkaline earth metal hydroxide compounds mentioned above. Examples include magnesium metal salts such as magnesium chloride, magnesium phosphate, and magnesium sulfate; calcium metal salts such as calcium chloride, calcium nitrate, calcium acetate, and calcium sulfate; aluminum metal salts such as aluminum chloride and aluminum sulfate; barium salts such as barium chloride, barium nitrate, and barium acetate; and zinc salts such as zinc chloride, zinc nitrate, and zinc acetate. Among these, magnesium metal salts, calcium metal salts, and aluminum metal salts are preferred, magnesium metal salts are more preferred, and magnesium chloride is particularly preferred. The method for reacting at least one selected from the alkali metal hydroxide and alkaline earth metal hydroxide mentioned above with the water-soluble polyvalent metal salt mentioned above in an aqueous medium is not particularly limited, but one method is to mix an aqueous solution of at least one selected from the alkali metal hydroxide and alkaline earth metal hydroxide with an aqueous solution of the water-soluble polyvalent metal salt.

[0060] The content of the dispersion stabilizer is not particularly limited, but is preferably 0.5 to 10 parts by mass, and more preferably 1.0 to 8.0 parts by mass, per 100 parts by mass of the total mass of the first polymerizable monomer and the hydrocarbon solvent. By having a dispersion stabilizer content above the lower limit, the monomer composition droplets can be sufficiently dispersed so that they do not coalesce in the suspension. On the other hand, by having a dispersion stabilizer content below the upper limit, it is possible to prevent the viscosity of the suspension from increasing during granulation and to avoid the problem of the suspension clogging the granulator. Furthermore, the content of the dispersion stabilizer is usually between 2 and 15 parts by mass, and preferably between 3 and 8 parts by mass, per 100 parts by mass of the aqueous medium.

[0061] (E)Aqueous medium In this disclosure, "aqueous medium" means a medium selected from the group consisting of water, a hydrophilic solvent, and a mixture of water and a hydrophilic solvent. The hydrophilic solvent in this disclosure is not particularly limited as long as it mixes well with water and does not undergo phase separation. Examples of hydrophilic solvents include alcohols such as methanol and ethanol; tetrahydrofuran (THF); and dimethyl sulfoxide (DMSO). Among aqueous media, water is preferred due to its high polarity. When using a mixture of water and a hydrophilic solvent, it is important that the overall polarity of the mixture does not become too low, from the viewpoint of forming droplets of the monomer composition. In this case, for example, the mixing ratio (mass ratio) of water and hydrophilic solvent may be water:hydrophilic solvent = 99:1 to 50:50.

[0062] A mixture is obtained by mixing the aforementioned materials and other materials as needed, and stirring as appropriate. In this mixture, the oil phase containing (A) the first polymerizable monomer, (B) an oil-soluble polymerization initiator, and (C) a lipophilic material such as a hydrocarbon solvent is dispersed in the aqueous phase containing (D) a dispersion stabilizer and (E) an aqueous medium, with particle sizes of several millimeters. Depending on the type of material, the dispersion state of these materials in the mixture can be observed with the naked eye. In the mixture preparation step, the mixture may be obtained by simply mixing the aforementioned materials and other materials as needed, and stirring as appropriate. However, in order to ensure a uniform shell, it is preferable to prepare the mixture by separately preparing an oil phase containing the first polymerizable monomer and a hydrocarbon solvent, and an aqueous phase containing a dispersion stabilizer and an aqueous medium, and then mixing these together. In this disclosure, a colloidal dispersion in which a poorly water-soluble inorganic dispersion stabilizer is dispersed in an aqueous medium in the form of colloidal particles can be preferably used as the aqueous phase. By preparing the oil phase and aqueous phase separately in this manner and then mixing them, hollow particles with a uniform shell composition can be produced.

[0063] (2) Suspension process The suspension step is a process of preparing a suspension in which droplets of a monomer composition containing a hydrocarbon solvent are dispersed in an aqueous medium by suspending the above-mentioned mixture. The suspension method for forming droplets of monomer compositions is not particularly limited, but can be carried out using equipment capable of strong stirring, such as (in-line) emulsifiers / dispersers (horizontal in-line dispersers such as Taiheiyo Kiko Co., Ltd., product name: Milder, and Eurotech Co., Ltd., product name: Cavitron; vertical in-line dispersers such as IKA, product name: DRS 2000 / 5, etc.) or high-speed emulsifiers / dispersers (product name: TK Homomixer MARK II, etc., manufactured by Primix Co., Ltd.). In the suspension prepared in the suspension process, droplets of a monomer composition containing the above-mentioned lipophilic material and having a particle size of approximately 1 to 30 μm are uniformly dispersed in an aqueous medium. Such droplets of monomer composition are difficult to observe with the naked eye and can be observed using known observation equipment such as an optical microscope. During the suspension process, phase separation occurs within the monomer composition droplets, causing the less polar hydrocarbon solvent to accumulate inside the droplets. As a result, the resulting droplets will have the hydrocarbon solvent distributed inside and other materials distributed around their periphery.

[0064] Figure 2 is a schematic diagram showing one embodiment of a suspension in the suspension process. The droplet 10 of the monomer composition in Figure 2 is schematically shown as its cross-section. Note that Figure 2 is merely a schematic diagram, and the suspension in this disclosure is not necessarily limited to that shown in Figure 2. Part of Figure 2 corresponds to Figure 1(2) described above. Figure 2 shows how droplets 10 of the monomer composition and the first polymerizable monomer 4c dispersed in the aqueous medium 1 are dispersed in the aqueous medium 1. The droplets 10 are formed by a dispersion stabilizer 3 surrounding the oil-soluble monomer composition 4. The monomer composition contains an oil-soluble polymerization initiator 5, as well as a first polymerizable monomer and a hydrocarbon solvent (neither of which are shown). The droplet 10 is a micro-oil droplet containing the monomer composition 4, and the oil-soluble polymerization initiator 5 generates polymerization initiation radicals within the micro-oil droplet. Therefore, precursor particles of the desired particle size can be produced without over-growing the micro-oil droplets. In suspension polymerization using such an oil-soluble polymerization initiator, there is no opportunity for the polymerization initiator to come into contact with the polymerizable monomer 4c dispersed in the aqueous medium 1. Therefore, by using an oil-soluble polymerization initiator, it is possible to suppress the formation of extra resin particles, such as relatively small, dense particles, in addition to the desired hollow resin particles.

[0065] (3) Polymerization process (3-1) First polymerization step In the above manufacturing method, the polymerization process is carried out in two stages. In the first polymerization step, a first polymerization reaction is carried out in which the suspension is subjected to a polymerization reaction until the polymerization conversion rate of the first polymerizable monomer is 93% by mass or more, thereby preparing a first precursor composition containing a shell containing a polymer of the first polymerizable monomer and first precursor particles having a hollow portion filled with a hydrocarbon solvent. During the first polymerization reaction, droplets of the monomer composition are subjected to the polymerization reaction while encapsulating the hydrocarbon solvent, allowing the polymerization reaction to proceed easily while maintaining their shape. Therefore, the size and porosity of the resulting hollow particles can be easily adjusted by adjusting the amount of hydrocarbon solvent and the type of dispersion stabilizer during the first polymerization reaction. Furthermore, because the above-mentioned first polymerizable monomer and hydrocarbon solvent are used in combination, the polarity of the hydrocarbon solvent is low relative to the shell of the first precursor particle, and the hydrocarbon solvent does not readily accrete with the shell, so phase separation occurs sufficiently, and only one hollow portion tends to be formed.

[0066] In the first polymerization reaction, there are no particular limitations on the polymerization method; for example, batch, semi-continuous, or continuous methods can be used. In the first polymerization reaction, the polymerization temperature is preferably 40 to 80°C, and more preferably 50 to 70°C. Furthermore, in the first polymerization reaction, the heating rate when raising the temperature to the polymerization temperature is preferably 10°C / h to 60°C / h, and more preferably 15°C / h to 55°C / h. Furthermore, the reaction time for the first polymerization reaction is preferably 0.5 to 5 hours, and more preferably 1 to 3 hours.

[0067] In the above manufacturing method, the first polymerization reaction is carried out until the polymerization conversion rate of the first polymerizable monomer reaches 93% by mass or more, preferably 95% by mass or more, more preferably 97% by mass or more, and even more preferably 99% by mass or more. In this disclosure, the polymerization conversion rate is determined by formula (A) below, using the mass of the solid content of the first precursor particles obtained by the first polymerization reaction and the mass of the first polymerizable monomer remaining unreacted after the first polymerization reaction. In this disclosure, the solid content refers to all components excluding the solvent, and liquid polymerizable monomers, etc., are included in the solid content. The mass of the unreacted first polymerizable monomer can be measured using gas chromatography (GC). Polymerization conversion rate (mass%) = 100 - (mass of unreacted primary polymerizable monomer / mass of solid content of primary precursor particles) × 100 Equation (A)

[0068] (3-2) Second polymerization step In the second polymerization step, a second polymerizable monomer having a solubility of 0.3 g / L or more in distilled water at 20°C is added to the first precursor composition obtained in the first polymerization step, and a second polymerization reaction is carried out to prepare a second precursor composition containing a shell containing polymers of the first polymerizable monomer and the second polymerizable monomer, and second precursor particles having a hollow portion filled with a hydrocarbon solvent. In the second polymerization reaction, the polymerization proceeds with the second polymerizable monomer incorporated into the shell of the first precursor particle. As the incorporation of the second polymerizable monomer into the shell of the first precursor particle promotes thermal motion, it is presumed that in the second polymerization reaction, the polymerization reaction of the polymerizable functional groups of the first polymerizable monomer that remained unreacted within the shell, and the polymerization of the second polymerizable monomer proceeds, forming a dense crosslinked structure.

[0069] The second polymerizable monomer is not particularly limited as long as it is a polymerizable monomer with a solubility of 0.3 g / L or more in distilled water at 20°C. However, among these, non-crosslinked monomers with a solubility of 0.3 g / L or more in distilled water at 20°C, i.e., hydrophilic non-crosslinked monomers, are preferred in order to improve the strength and solvent resistance of the hollow particles and to enhance the effects of heat insulation and weight reduction provided by the hollow particles. Examples of hydrophilic non-crosslinked monomers used as the second polymerizable monomer include those similar to those that can be used as the first polymerizable monomer. In particular, from the standpoint of improving the strength and solvent resistance of hollow particles and enhancing the effects of heat insulation and weight reduction provided by hollow particles, at least one selected from the group consisting of alkyl (meth)acrylates having an alkyl group having 1 to 5 carbon atoms, nitrile (meth)acrylates and their derivatives, and non-crosslinkable monomers containing polar groups is preferred, alkyl (meth)acrylates having an alkyl group having 1 to 5 carbon atoms are more preferred, and alkyl (meth)acrylates having an alkyl group having 1 to 4 carbon atoms are even more preferred. The alkyl acrylates and nitrile acrylates mentioned above are preferred, respectively. When the polymerizable functional group is an acryloyl group instead of a methacryloyl group, the reactivity is excellent, which improves the effects of heat insulation and weight reduction due to the hollow particles, and also makes it less likely for unreacted second polymerizable monomers to remain. In this disclosure, the acrylic crosslinkable monomer may be any crosslinkable monomer having at least one acryloyl group as a polymerizable functional group and no methacryloyl group, but it is preferable that all polymerizable functional groups are acryloyl groups. Furthermore, the number of carbon atoms in the alkyl group of the above-mentioned alkyl (meth)acrylates is preferably 1 to 4, from the viewpoint of improving the effects of heat insulation and weight reduction due to hollow particles, more preferably 1 to 3, from the viewpoint of preventing the residue of unreacted second polymerizable monomers, and even more preferably the alkyl group is a methyl group. Among the above polar group-containing non-crosslinkable monomers, epoxy group-containing monomers, hydroxyl group-containing monomers, and amino group-containing monomers are preferred. Among the epoxy group-containing monomers among the above polar group-containing non-crosslinkable monomers, glycidyl (meth)acrylate is preferred, and among the hydroxyl group-containing monomers, 2-hydroxyethyl methacrylate is preferred.

[0070] Furthermore, as the second polymerizable monomer, a hydrophilic crosslinkable monomer having a solubility of 0.3 g / L or more in distilled water at 20°C can also be used. Examples of hydrophilic crosslinkable monomers used as the second polymerizable monomer include those similar to those usable as the first polymerizable monomer. Among the hydrophilic crosslinkable monomers used as the second polymerizable monomer, hydrophilic crosslinkable monomers containing a hydroxyl group or an amino group are preferred. As a hydrophilic crosslinkable monomer containing a hydroxyl group, for example, 2-hydroxy-3-methacrylate is preferably used, and as a hydrophilic crosslinkable monomer containing an amino group, for example, diallylamine is preferably used. Furthermore, the second polymerizable monomer is preferably 2 g / L or more, more preferably 10 g / L or more, and even more preferably 15 g / L or more, in distilled water at 20°C, because the second polymerizable monomer is easily incorporated into the shell of the first precursor particles, promoting thermal motion and improving the strength of the hollow particles. The upper limit of the solubility of the second polymerizable monomer in distilled water at 20°C is not particularly limited, but is usually 80 g / L or less.

[0071] Furthermore, the molecular weight of the second polymerizable monomer is preferably 200 or less, more preferably 100 or less, as the second polymerizable monomer is more easily incorporated into the shell of the first precursor particles, thereby promoting thermal motion, improving the strength and solvent resistance of the hollow particles, and enhancing the effects of heat insulation and weight reduction provided by the hollow particles. The lower limit of the molecular weight of the second polymerizable monomer is not particularly limited, but is usually 50 or more.

[0072] The amount of the second polymerizable monomer added is preferably 3 to 15 parts by mass, and more preferably 4 to 10 parts by mass, per 100 parts by mass of the first polymerizable monomer. If the amount of the second polymerizable monomer added is above the lower limit, the effect of promoting the polymerization reaction by adding the second polymerizable monomer is improved, and the crosslinked structure of the hollow particle shell becomes denser, thereby improving the strength and solvent resistance of the hollow particle, and consequently improving the effects of heat insulation and weight reduction of the hollow particle. On the other hand, if the amount of the second polymerizable monomer added is below the upper limit, it is possible to suppress the decrease in the content ratio of the first polymerizable monomer to the total polymerizable monomer used to form the shell. Since the first polymerizable monomer contains a large amount of crosslinkable monomers, by suppressing the decrease in the content ratio of the first polymerizable monomer, it is possible to obtain hollow particles with excellent strength that contain a large amount of crosslinked structure formed by crosslinkable monomers.

[0073] In the second polymerization reaction, which is carried out after adding the second polymerizable monomer, there are no particular limitations on the polymerization method; for example, the same polymerization method used in the first polymerization reaction can be employed. In the second polymerization reaction, the polymerization temperature is preferably 40 to 80°C, and more preferably 50 to 70°C. The reaction time for the second polymerization reaction is preferably 1 to 6 hours, and more preferably 2 to 4 hours.

[0074] According to the above manufacturing method, the amount of unreacted polymerizable monomers remaining after the second polymerization reaction can be preferably 750 ppm or less, more preferably 500 ppm or less, and even more preferably 300 ppm or less. If the amount of unreacted polymerizable monomers remaining after the second polymerization reaction is below the above upper limit, it is suggested that the reaction rate of polymerizable monomers is high. When the reaction rate of polymerizable monomers is high, the cross-linking structure in the shell tends to become denser, which in turn tends to improve the solvent resistance and strength of the hollow particles. In this disclosure, the amount of unreacted polymerizable monomers remaining after the second polymerization reaction is the ratio of the mass of unreacted polymerizable monomers to the mass of solids of the hollow particles obtained by the second polymerization reaction. The mass of unreacted polymerizable monomers can be measured using gas chromatography (GC).

[0075] (4) Solid-liquid separation process This step involves obtaining a solid component containing the second precursor particles by performing solid-liquid separation of the second precursor composition, which contains hollow particles (second precursor particles) encapsulating a hydrocarbon solvent, obtained by the polymerization step described above.

[0076] The method for solid-liquid separation of the second precursor composition is not particularly limited, and known methods can be used. Examples of solid-liquid separation methods include centrifugation, filtration, and static separation. Among these, centrifugation or filtration can be used, and centrifugation may be used from the viewpoint of ease of operation. After the solid-liquid separation process, any optional steps such as a pre-drying process may be performed before carrying out the solvent removal process described later. An example of a pre-drying process is to pre-dry the solid obtained after the solid-liquid separation process using a drying device such as a dryer or a drying apparatus such as a hand dryer.

[0077] (5) Solvent removal process This step involves removing the hydrocarbon solvent contained within the hollow particles (second precursor particles) obtained in the solid-liquid separation step. By removing the hydrocarbon solvent encapsulated within the second precursor particle in the air, the hydrocarbon solvent inside the second precursor particle is replaced with air, resulting in a hollow particle filled with gas.

[0078] In this process, "in the air" strictly refers to an environment where there is absolutely no liquid outside the second precursor particles, or an environment where there is only a very small amount of liquid outside the second precursor particles that does not affect the removal of the hydrocarbon solvent. "In the air" can also be rephrased as a state in which the second precursor particles are not in the slurry, or a state in which the second precursor particles are in the dry powder. In other words, in this process, it is important to remove the hydrocarbon solvent in an environment in which the second precursor particles are in direct contact with the external gas.

[0079] The method for removing the hydrocarbon solvent from the second precursor particles in the air is not particularly limited, and known methods can be employed. Examples of such methods include vacuum drying, heat drying, airflow drying, or a combination of these methods. In particular, when using the heat drying method, the heating temperature must be above the boiling point of the hydrocarbon solvent and below the maximum temperature at which the shell structure of the second precursor particles does not collapse. Therefore, depending on the shell composition in the second precursor particles and the type of hydrocarbon solvent, the heating temperature may be, for example, 50-200°C, 70-200°C, or 100-200°C. Through a drying process in air, the hydrocarbon solvent inside the second precursor particle is replaced by the external gas, resulting in hollow particles in which the hollow portion is filled with gas.

[0080] The drying atmosphere is not particularly limited and can be appropriately selected depending on the application of the hollow particles. Examples of suitable drying atmospheres include air, oxygen, nitrogen, and argon. Furthermore, hollow particles with a temporarily vacuumed interior can be obtained by first filling the inside of the hollow particles with gas and then drying them under reduced pressure.

[0081] Alternatively, instead of performing solid-liquid separation on the slurry-like second precursor composition obtained in the polymerization step, the hydrocarbon solvent may be removed by replacing the hydrocarbon solvent encapsulated in the second precursor particles with the aqueous medium of the slurry in a slurry containing the second precursor particles and an aqueous medium. In this method, the hydrocarbon solvent encapsulated in the second precursor particles can be removed by bubbling an inert gas through the second precursor composition at a temperature at or above the boiling point of the hydrocarbon solvent minus 35°C. Here, if the hydrocarbon solvent is a mixed solvent containing multiple types of hydrocarbon solvents and has multiple boiling points, the boiling point of the hydrocarbon solvent in the solvent removal step shall be the boiling point of the solvent with the highest boiling point among the solvents contained in the mixed solvent, i.e., the highest boiling point among the multiple boiling points. The temperature at which the inert gas is bubbling through the second precursor composition is preferably at or above the boiling point of the hydrocarbon solvent minus 30°C, and more preferably at or above the boiling point of the hydrocarbon solvent minus 20°C, in order to reduce the amount of residual hydrocarbon solvent in the hollow particles. The bubbling temperature is usually at or above the polymerization temperature in the polymerization step. Although not particularly limited, the bubbling temperature may be between 50°C and 100°C. The inert gas used for bubbling is not particularly limited, but examples include nitrogen and argon. The bubbling conditions are adjusted as appropriate to remove the hydrocarbon solvent encapsulated in the second precursor particles, depending on the type and amount of hydrocarbon solvent, and are not particularly limited. For example, an inert gas may be bubbled at a rate of 1 to 3 L / min for 1 to 10 hours. In this method, an aqueous slurry is obtained in which a water-based medium is encapsulated within the second precursor particles. By separating this slurry into solid and liquid phases and drying the resulting hollow particles, the water-based medium within the hollow particles is removed, thereby obtaining hollow particles in which the hollow portion is occupied by gas.

[0082] Comparing a method in which a slurry-like second precursor composition is subjected to solid-liquid separation and then the hydrocarbon solvent in the second precursor particles is removed in the air to obtain hollow particles with a hollow portion filled with gas, with a method in which the hydrocarbon solvent contained in the second precursor particles is replaced with the aqueous medium of the slurry in a slurry containing the second precursor particles and an aqueous medium, then solid-liquid separation is performed and the aqueous medium in the second precursor particles is removed in the air to obtain hollow particles with a hollow portion filled with gas, the former method has the advantage that the hollow particles are less likely to be crushed in the step of removing the hydrocarbon solvent, while the latter method has the advantage that the residue of hydrocarbon solvent is reduced by performing bubbling with an inert gas. Furthermore, when replacing the hydrocarbon solvent encapsulated in the second precursor particle with water, there is a problem that the resulting hollow resin particles will collapse unless an equal volume of water is added to the particle to replace the hydrocarbon solvent removed from it. To prevent this, for example, the pH of the slurry can be set to 7 or higher, and the hydrocarbon solvent can be removed after the particle shell has been alkaline-swelled. In this case, the particle shell gains flexibility, allowing the replacement of the hydrocarbon solvent with water inside the particle to proceed rapidly.

[0083] In addition, after the polymerization step and before the solid-liquid separation step, a method may be used to remove the hydrocarbon solvent contained within the second precursor particles without performing solid-liquid separation of the slurry-like second precursor composition obtained in the polymerization step. For example, this could involve evaporating the hydrocarbon solvent contained within the second precursor particles from the second precursor composition under a predetermined pressure (high pressure, atmospheric pressure, or reduced pressure); or introducing an inert gas such as nitrogen, argon, or helium, or water vapor, into the second precursor composition under a predetermined pressure (high pressure, atmospheric pressure, or reduced pressure) and then evaporating the solvent.

[0084] (6) Others In addition to the above steps (1) to (5), other steps such as the cleaning step (6-a) and the re-replacement step (6-b) of the hollow section may be added. (6-a) Washing process The washing step is a step performed before the solid-liquid separation step in order to remove any remaining dispersion stabilizer in the second precursor composition containing the second precursor particles by adding an acid or alkali. If the dispersion stabilizer used is an inorganic dispersion stabilizer soluble in acid, it is preferable to wash the second precursor composition containing the second precursor particles by adding an acid. On the other hand, if the dispersion stabilizer used is an inorganic compound soluble in alkali, it is preferable to wash the second precursor composition containing the second precursor particles by adding an alkali. Furthermore, when an acid-soluble inorganic dispersion stabilizer is used as the dispersion stabilizer, it is preferable to add an acid to the second precursor composition containing the second precursor particles and adjust the pH to preferably 6.5 or lower, more preferably 6 or lower. As the added acid, inorganic acids such as sulfuric acid, hydrochloric acid, and nitric acid, and organic acids such as formic acid and acetic acid can be used, but sulfuric acid is particularly preferred because it has a high efficiency in removing the dispersion stabilizer and places little burden on the manufacturing equipment.

[0085] (6-b) Replacement process of the hollow section The hollow portion re-substitution process is a process of replacing the gas or liquid inside a hollow particle with another gas or liquid. Such substitution can change the environment inside the hollow particle, selectively confine molecules inside the hollow particle, or modify the chemical structure inside the hollow particle to suit the application.

[0086] 3. Applications of thermal conductivity modifiers The thermal conductivity modifiers of this disclosure can be used in any application where adjustment of thermal conductivity is required, and are not particularly limited. For example, the thermal conductivity modifiers of this disclosure can be suitably used as additives to paints, paper, information recording paper, various containers, 3D printer filaments, etc., or as additives to heat insulating films or thermoelectric conversion materials used in various fields such as automobiles, bicycles, aircraft, ships, railway vehicles, space, architecture, electrical, electronics, sporting goods, footwear, home appliance parts, stationery, tools, etc. Specifically in the field of electrical or electronics, the thermal conductivity modifiers of this disclosure can be used as additives to semiconductor materials such as electronic circuit boards, interlayer insulating materials, dry film resists, solder resists, bonding wires, magnet wires, semiconductor encapsulants, epoxy encapsulants, mold underfills, underfills, die bond pastes, buffer coat materials, copper-clad laminates, flexible substrates, high-frequency device modules, antenna modules, and automotive radars. Furthermore, a component to which the thermal conductivity modifier of this disclosure is added not only has reduced thermal conductivity but also increased reflectivity, resulting in less absorption of heat from the outside and improved heat resistance. Therefore, the thermal conductivity modifier of this disclosure can be suitably used as an additive to reduce thermal conductivity and improve heat resistance in components that do not require low reflectivity or components that require increased reflectivity. Conventionally, additives such as titanium dioxide have been used to increase reflectivity, but by using the thermal conductivity modifier of this disclosure, it is possible to increase reflectivity while also achieving heat insulation and weight reduction. Examples of applications where low reflectivity is not required or where increased reflectivity is required and thermal conductivity adjustment is necessary include paints, as well as various fields such as automobiles, aircraft, ships, railway vehicles, space, architecture, electrical and electronics. Furthermore, the thermal conductivity modifier of this disclosure has excellent strength and is resistant to crushing during mixing with other materials and during molding after mixing, making it suitable as an additive for molded articles, and particularly suitable for use as an additive for resin molded articles.

[0087] 4.Resin composition The resin composition of this disclosure is characterized by containing the thermal conductivity modifier of this disclosure and a matrix resin. Using the resin composition of this disclosure, a molded article of this disclosure with reduced thermal conductivity can be produced. The thermal conductivity modifier of this disclosure has a hollow particle form, yet solvents do not easily penetrate the inside of the particles, and furthermore, it has excellent strength. Therefore, even when the resin composition of this disclosure contains a solvent (varnish), the thermal conductivity modifier of this disclosure is less likely to deform or collapse in the resin composition, during molding of the resin composition, and in the molded article after molding, and the voids inside the particles are maintained. As a result, the resin composition of this disclosure and the molded article formed using the resin composition of this disclosure have reduced thermal conductivity.

[0088] The matrix resin used in the resin composition of this disclosure is not particularly limited, but may include a thermoplastic resin, a thermosetting resin, or a room-temperature curing resin. The thermoplastic resin can be any known material and is not particularly limited, but examples include polyolefins such as polypropylene and polyethylene; polyamides such as PA6, PA66, and PA12; polyimide, polyamideimide, polyetherimide, polyetherketone, polyvinyl chloride, polystyrene, poly(meth)acrylate, polycarbonate, polyvinylidene fluoride, acrylonitrile-butadiene-styrene copolymer (ABS), acrylonitrile-styrene copolymer (AS), polyphenylene ether, polyphenylene sulfide, polyester, polytetrafluoroethylene, thermoplastic elastomer, and the like. These thermoplastic resins can be used individually or in combination of two or more. The thermosetting resin can be any known resin and is not particularly limited, but examples include phenolic resins, melamine resins, urea resins, unsaturated polyester resins, epoxy resins, polyurethane resins, silicon resins, alkyd resins, thermosetting polyphenylene ether resins, thermosetting polyimide resins, benzoxazine resins, urea resins, allyl resins, aniline resins, maleimide resins, bismaleimidotriazine resins, liquid crystalline polyester resins, vinyl ester resins, unsaturated polyester resins, cyanate ester resins, polyetherimide resins, and the like. These thermosetting resins can be used individually or in combination of two or more. The aforementioned room-temperature curing resin can be any known resin, and is not particularly limited; examples include epoxy resins and urethane resins. These room-temperature curing resins can be used individually or in combination of two or more. Examples of preferred matrix resins used in the resin compositions of this disclosure include those containing epoxy resins. Examples of epoxy resins include bixylenol-type epoxy resins, bisphenol A-type epoxy resins, bisphenol F-type epoxy resins, bisphenol S-type epoxy resins, bisphenol AF-type epoxy resins, dicyclopentadiene-type epoxy resins, trisphenol-type epoxy resins, naphthol novolac-type epoxy resins, phenol novolac-type epoxy resins, tert-butyl-catechol-type epoxy resins, naphthalene-type epoxy resins, naphthol-type epoxy resins, anthracene-type epoxy resins, glycidylamine-type epoxy resins, and glycidyl ester-type epoxy resins. Examples include cresol novolac type epoxy resins, phenol aralkyl type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiroring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexanedimethanol type epoxy resins, naphthylene ether type epoxy resins, trimethylol type epoxy resins, tetraphenylethane type epoxy resins, isocyanurate type epoxy resins, phenolphthalein type epoxy resins, and the like. These epoxy resins can be used individually or in combination of two or more types.

[0089] The matrix resin may optionally contain additives for curing the resin, such as curing agents, curing catalysts, or curing accelerators. These resin curing additives can be selected from known sources depending on the type of resin and are not particularly limited. Examples include amines, acid anhydrides, imidazoles, thiols, phenols, naphthols, benzoxazines, cyanate esters, and carbodiimides. Examples of curing agents used in combination with epoxy resins include amine-based curing agents, amide-based curing agents, acid anhydride-based curing agents, phenol-based curing agents, active ester-based curing agents, carboxyl group-containing curing agents, and thiol-based curing agents. Furthermore, examples of curing catalysts used in combination with epoxy resins include phosphorus compounds, tertiary amine compounds, imidazole compounds, and organometallic salts. These additives for curing the resins can be used individually or in combination of two or more.

[0090] The matrix resin content is not particularly limited, but is preferably 50 to 95% by mass of the total solids content of the resin composition of this disclosure. When the matrix resin content is above the lower limit, the moldability of the resin composition when it is made into a molded article is excellent, and the resulting molded article has excellent mechanical strength. On the other hand, when the matrix resin content is below the upper limit, the thermal conductivity modifier of this disclosure can be sufficiently included, and the thermal conductivity of the resin composition can be sufficiently reduced. In this disclosure, the content of the matrix resin also includes the content of additives for curing the resin, such as curing agents, curing catalysts, or curing accelerators.

[0091] The content of the thermal conductivity modifier in this disclosure is not particularly limited, but is preferably 5 to 50% by mass of the total solids content of the resin composition in this disclosure. By having a thermal conductivity modifier content above the lower limit, the thermal conductivity of the resin composition can be sufficiently reduced. On the other hand, by having a thermal conductivity modifier content below the upper limit, the matrix resin can be sufficiently contained, thereby improving moldability and mechanical strength.

[0092] Furthermore, the resin composition of this disclosure may further contain a solvent for dissolving or dispersing each component, if necessary. The presence of a solvent in the resin composition of this disclosure is preferable because it facilitates the acquisition of the thermal insulation effect provided by the thermal conductivity modifier of this disclosure. The solvent used in the resin composition of this disclosure can be any known solvent usable in resin compositions, and is not particularly limited, but for example, aromatic hydrocarbons such as benzene, toluene, and xylene; ketones such as dioxane, acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; and ethers such as ethylene glycol monomethyl ether and propylene glycol monomethyl ether can be preferably used. These solvents can be used individually or in combination of two or more. In particular, the solvent preferably contains at least one selected from ketones and ethers, and more preferably contains ketones, in order to easily exhibit the effects of thermal insulation and weight reduction by the thermal conductivity modifier of this disclosure.

[0093] If the resin composition of this disclosure contains a solvent, the solvent content is not particularly limited and can be adjusted as appropriate depending on the application. In order to easily exhibit the effects of heat insulation and weight reduction by the heat conduction modifier of this disclosure, the solvent content is preferably 10 to 50% by mass, more preferably 20 to 40% by mass, of 100% by mass of the total mass of the resin composition.

[0094] The resin compositions of this disclosure may further contain additives such as ultraviolet absorbers, colorants, defoamers, thickeners, heat stabilizers, leveling agents, lubricants, antistatic agents, and fillers, as needed, to the extent that they do not impair the effects of this disclosure.

[0095] The resin composition of the present disclosure can be obtained, for example, by mixing the thermal conductivity modifier of the present disclosure with a matrix resin and solvents and additives which may be added as needed. If the resin composition contains a solvent, the mixing should be carried out within a temperature range in which the solvent does not volatilize, for example, above room temperature but below the boiling point of the solvent. Furthermore, if the resin composition contains a thermosetting resin as a matrix resin, the mixing should be carried out in a temperature environment below the curing temperature of the thermosetting resin, and is not particularly limited, but is usually carried out in a temperature environment of 240°C or lower. When the resin composition includes a thermoplastic resin as the matrix resin, the mixing may be performed by melt kneading, which involves heating the resin composition to melt the thermoplastic resin. The temperature during melt kneading should be any temperature that can melt the thermoplastic resin used, and is not particularly limited, but it is preferably 250°C or lower in order to suppress the crushing of the thermal conductivity modifier.

[0096] 5. Molded body The molded article of this disclosure is characterized by containing the thermal conductivity modifier of this disclosure. The molded article of this disclosure contains the thermal conductivity modifier of this disclosure, and therefore its thermal conductivity is reduced. The molded article of this disclosure preferably has a thermal conductivity of 0.175 W / m·K or less, and more preferably 0.150 W / m·K or less.

[0097] The molded article of this disclosure may have a higher reflectance compared to one without the thermal conductivity modifier, due to the inclusion of the thermal conductivity modifier described herein. The molded article of this disclosure preferably has a reflectance of 50% or more at 420 nm, and more preferably 60% or more. Furthermore, the molded article of this disclosure preferably has a reflectance of 60% or more at 580 nm, and more preferably 80% or more. The reflectance of the molded article of this disclosure in the wavelength range from 320 nm to 820 nm is 100% or less, and there is no particular upper limit.

[0098] The molded articles of this disclosure are typically molded articles of the resin compositions of this disclosure described above. If the resin composition of this disclosure is a liquid resin composition containing hollow particles or the like in a liquid matrix resin before curing, or a liquid resin composition obtained by dissolving or dispersing each component in a solvent, a molded article can be obtained by applying the liquid resin composition to a support and drying and curing it as necessary. Examples of materials for the support include resins such as polyethylene terephthalate and polyethylene naphthalate; and metals such as copper, aluminum, nickel, chromium, gold, and silver. Known methods can be used to apply the liquid resin composition, including, for example, dip coating, roll coating, curtain coating, die coating, slit coating, and gravure coating. If the liquid resin composition contains a solvent, it is preferable to dry the resin composition after application. The drying temperature is preferably such that the matrix resin does not harden, and is typically 20°C to 200°C, preferably 30°C to 150°C. The drying time is typically 30 seconds to 1 hour, preferably 1 minute to 30 minutes. The curing reaction of the resin composition is carried out by a method appropriate to the type of matrix resin and is not particularly limited. When a matrix resin that hardens by heating is included, the heating temperature for the curing reaction is adjusted appropriately according to the type of resin and is not particularly limited, but is usually 30°C to 400°C, preferably 70°C to 300°C, and more preferably 100°C to 200°C. The curing time is 5 minutes to 5 hours, preferably 30 minutes to 3 hours. The heating method is not particularly limited and can be carried out using, for example, an electric oven. The matrix resin contained in the liquid resin composition, which is obtained by dissolving or dispersing each component in a solvent, may be a thermosetting resin, a room-temperature curing resin, or a thermoplastic resin.

[0099] On the other hand, when the resin composition of the present disclosure contains the thermoplastic resin, for example, a molded article of the resin composition of the present disclosure can be obtained by melt-kneading the resin composition and then molding it into a desired shape using a known molding method such as extrusion molding, injection molding, press molding, or compression molding. Since the thermal conductivity modifier in the form of hollow particles in the resin composition of the present disclosure is not easily crushed, even when using molding methods performed under heating and pressurizing conditions such as injection molding or compression molding, crushing of the thermal conductivity modifier is suppressed, and a molded article with reduced thermal conductivity can be obtained.

[0100] The shape of the molded body is not particularly limited and can be any shape, such as a sheet, film, plate, tube, or any other three-dimensional shape.

[0101] The applications of the molded articles of this disclosure are not particularly limited, but they can be used in various fields such as automobiles, bicycles, aircraft, ships, railway vehicles, space, architecture, electrical and electronic equipment, various containers, sporting goods, footwear, home appliance parts, stationery, and tools. Since the molded articles of this disclosure have reduced thermal conductivity, they can be used in the above-mentioned fields, for example, as thermal insulation films or thermoelectric conversion materials. [Examples]

[0102] The present disclosure will be further described below with reference to examples and comparative examples, but the present disclosure is not limited to these examples. Parts and percentages are by mass unless otherwise specified.

[0103] [Example 1] (1) Mixed liquid preparation process First, the following materials were mixed to form the oil phase. First polymerizable monomer: 80 parts ethylene glycol dimethacrylate and 20 parts pentaerythritol tetraacrylate 2,2'-Azobis(2,4-dimethylvaleronitrile) (oil-soluble polymerization initiator, manufactured by Wako Pure Chemical Industries, Ltd., trade name: V-65) 3 parts Cyclohexane 125 parts Next, in a stirred tank, under room temperature (25°C) conditions, an aqueous solution prepared by dissolving 17.1 parts of magnesium chloride (water-soluble polyvalent metal salt) in 494 parts of deionized water was gradually added under stirring to an aqueous solution prepared by dissolving 12.1 parts of sodium hydroxide (alkali metal hydroxide) in 121 parts of deionized water to prepare a magnesium hydroxide colloid (poorly water-soluble metal hydroxide colloid) dispersion (4 parts magnesium hydroxide), which was then used as the aqueous phase. A mixture was prepared by mixing the obtained aqueous phase and oil phase.

[0104] (2) Suspension process The mixture obtained in the above mixture preparation step was suspended by stirring it for 1 minute at a rotation speed of 4,000 rpm using a disperser (Primix Corporation, product name: Homomixer) to prepare a suspension in which droplets of the monomer composition containing cyclohexane were dispersed in water.

[0105] (3) Polymerization process The suspension obtained in the above suspension step was heated in a nitrogen atmosphere from 40°C to 65°C over 30 minutes (heating rate: 50°C / hour), and stirred for 1 hour and 30 minutes under the temperature of 65°C to carry out the first polymerization reaction, obtaining a first precursor composition containing the first precursor particles. The polymerization conversion rate at the end of the first polymerization reaction was 99.2% by mass. Subsequently, 5 parts of methyl acrylate as the second polymerizable monomer were added to the stirring tank, and the second polymerization reaction was carried out by stirring for 2 hours and 30 minutes under the nitrogen atmosphere and temperature of 65°C. This second polymerization reaction obtained a second precursor composition containing the second precursor particles encapsulating cyclohexane.

[0106] (4) Washing process and solid-liquid separation process The second precursor composition described above was washed with dilute sulfuric acid (25°C, 10 minutes) to reduce the pH to 5.5 or less. Next, after separating the water by filtration, 200 parts of freshly deionized water were added to re-form a slurry, and the water washing treatment (washing, filtration, dewatering) was repeated several times at room temperature, and the solid was separated by filtration to obtain the solid. The obtained solid was dried in a dryer at a temperature of 40°C to obtain second precursor particles containing cyclohexane.

[0107] (5) Solvent removal process The second precursor particles obtained in the solid-liquid separation process described above were heat-treated in a vacuum dryer at 200°C under vacuum conditions for 6 hours to remove the hydrocarbon solvent contained within the particles, thereby obtaining the thermal conductivity modifier of Example 1. Based on observations using a scanning electron microscope and porosity values, the obtained thermal conductivity modifier was confirmed to have the morphology of spherical, hollow particles with hollow sections.

[0108] [Example 2] In Example 1, the thermal conductivity modifier of Example 2 was manufactured using the same procedure as in Example 1, except that the amount of cyclohexane added in the "(1) Mixture Preparation Step" was changed to 160 parts.

[0109] [Examples 3-8] Except for the type or amount of the second polymerizable monomer added in the "(3) polymerization step" in Example 1, the thermal conductivity modifiers of Examples 3 to 8 were manufactured using the same procedure as in Example 1.

[0110] [Comparative Example 1] In Example 1, the thermal conductivity modifier of Comparative Example 1 was produced using the same procedure as in Example 1, except that the second polymerizable monomer was not added and the second polymerization reaction was not carried out in the "(3) polymerization step" described above.

[0111] [Comparative Example 2] In Example 1, the thermal conductivity modifier of Comparative Example 2 was produced using the same procedure as in Example 1, except that in the "(3) Polymerization step" described above, the reaction time of the first polymerization reaction was changed from 1 hour 30 minutes to 30 minutes, and when the total polymerization conversion rate of the first polymerizable monomers, ethylene glycol dimethacrylate and pentaerythritol tetraacrylate, reached 91.0% by mass, the second polymerizable monomer was added and the second polymerization reaction was carried out.

[0112] [Comparative Example 3] In Example 1, the thermal conductivity modifier of Comparative Example 3 was manufactured using the same procedure as in Example 1, except that the materials and quantities of the first polymerizable monomer in the "(1) Mixture Preparation Step" were as shown in Table 1.

[0113] [Comparative Example 4] In Example 1, the thermal conductivity modifier of Comparative Example 4 was produced using the same procedure as in Example 1, except that in the "(3) polymerization step" described above, 5 parts of styrene (solubility in distilled water at 20°C is 0.2 g / L) was added as the second polymerizable monomer instead of 5 parts of methyl acrylate.

[0114] [Table 1]

[0115] [Evaluation] 1. Polymerization Conversion Rate In the polymerization step of each Example and each Comparative Example, 50 g of the first precursor composition produced in the first polymerization reaction was collected and filtered under pressure to obtain first precursor particles (containing water and a hydrocarbon solvent) contained in the first precursor composition, and the particles were accurately weighed to the 1 mg unit. To about 3 g of the accurately weighed first precursor particles, 27 g of ethyl acetate was added, followed by stirring for 15 minutes, and then 13 g of methanol was added, followed by further stirring for 10 minutes. The resulting solution was allowed to stand to precipitate insoluble matter, and the supernatant of this solution was collected as a measurement sample. 2 μL of the measurement sample was injected into a gas chromatograph, and the amount of polymerizable monomer in the measurement sample was quantified by gas chromatography (GC) under the following conditions, which was taken as the mass of unreacted first polymerizable monomer. Further, the first precursor particles obtained by pressure filtration were dried at 200°C for 2 hours to remove water and the hydrocarbon solvent, and the mass of the solid content of the first precursor particles was determined. Then, the polymerization conversion rate was calculated by the following formula (A). Polymerization conversion rate (mass%) = 100-(mass of unreacted first polymerizable monomer / mass of solid content of first precursor particles) × 100 Formula (A) <GC Conditions> Column: TC-WAX (0.25 mm × 30 m) Column temperature: 80°C Injection temperature: 200°C FID detector side temperature: 200°C

[0116] 2. Residual Monomer Amount 3 g of hollow particles was accurately weighed to the 1 mg unit, 27 g of ethyl acetate was added, followed by stirring for 15 minutes, and then 13 g of methanol was added, followed by further stirring for 10 minutes. The resulting solution was allowed to stand to precipitate insoluble matter, and the supernatant of this solution was collected as a measurement sample. 2 μL of the measurement sample was injected into a gas chromatograph, and the amount of unreacted polymerizable monomer in the measurement sample was quantified by gas chromatography (GC) under the following conditions. The content ratio of unreacted polymerizable monomer contained in the hollow particles was calculated and taken as the residual monomer amount. <GC Conditions> Column: TC-WAX (0.25 mm × 30 m) Column temperature: 80°C Injection temperature: 200°C FID detector temperature: 200°C

[0117] Table 2 shows the content ratio (mass%) of each monomer unit in the polymer contained in the shell, for the thermal conductivity modifiers in the form of hollow particles obtained in each of the examples and comparative examples. In addition, the following measurements and evaluations were performed on the thermal conductivity modifiers obtained in each of the examples and comparative examples. The results are shown in Table 2.

[0118] 3. Volume-average particle diameter The particle diameter of the hollow particles serving as the thermal conductivity modifier was measured using a laser diffraction particle size distribution analyzer (manufactured by Shimadzu Corporation, product name: SALD-2000), and the volume average thereof was calculated to obtain the volume-average particle diameter.

[0119] 4. Density and porosity 4-1. Measurement of apparent density First, a 100 cm 3 volumetric flask was filled with approximately 30 cm 3 of hollow particles serving as the thermal conductivity modifier, and the mass of the filled hollow particles was accurately weighed. Next, isopropanol was accurately filled up to the marked line in the volumetric flask containing the hollow particles while taking care not to introduce air bubbles. The mass of isopropanol added to the volumetric flask was accurately weighed, and the apparent density D1 (g / cm 3 ) of the hollow particles was calculated based on the following formula (I). Formula (I) Apparent density D1 = [mass of hollow particles] / (100 - [mass of isopropanol] ÷ [specific gravity of isopropanol at measurement temperature])

[0120] 4-2. Measurement of true density After pre-grinding the hollow particles, approximately 10 g of ground hollow particle fragments were filled into a 100 cm 3 volumetric flask, and the mass of the filled ground fragments was accurately weighed. Next, as with the measurement of apparent density above, isopropanol is added to a volumetric flask, the mass of isopropanol is accurately weighed, and the true density D0 (g / cm³) of the hollow particles is calculated based on the following formula (II). 3 ) was calculated. Formula (II) True density D0 = [Mass of hollow particle fragments] / (100 - [Mass of isopropanol] ÷ [Specific gravity of isopropanol at measurement temperature])

[0121] 4-3. Calculation of void ratio The porosity of the hollow particles was calculated from the apparent density D1 and true density D0 of the hollow particles based on the following equation (III). Formula (III) Porosity (%) = 100 - (Apparent density D1 / True density D0) × 100

[0122] 5. Immersion Test Under conditions of 25°C, 0.1 mg of hollow particles, a thermal conductivity modifier, was added to 4 mL of acetone. The mixture was shaken for 10 minutes at a shaking speed of 100 rpm using a shaker, and then allowed to stand for 48 hours. The proportion of precipitated hollow particles was determined and evaluated according to the following evaluation criteria. The precipitated hollow particles were separated from the acetone using a centrifuge, dried, and their mass was measured. The proportion of precipitated hollow particles was determined by calculating the ratio of the mass of the precipitated hollow particles to the total mass of the hollow particles immersed in the acetone. (Evaluation criteria for immersion tests) ○: Less than 5% by mass of precipitated hollow particles ×: Precipitated hollow particles make up 5% or more by mass.

[0123] [Table 2]

[0124] [Consideration] As shown in Table 2 above, the thermal conductivity modifiers in the form of hollow particles obtained in Comparative Examples 1 to 4 had a precipitate of 5% by mass or more of hollow particles in acetone during the immersion test described above. In Comparative Example 1, because the polymerization reaction was carried out in a single step, unreacted polymerizable functional groups remained in the shell, and the cross-linking structure of the shell was rough. Therefore, it is presumed that the resulting hollow particles were easily permeated with acetone. In Comparative Example 2, the second polymerizable monomer was added before the polymerization conversion rate of the first polymerizable monomer reached 93% by mass. Therefore, it is presumed that the timing of adding the second polymerizable monomer was too early, resulting in unreacted polymerizable functional groups remaining in the shell and a rough cross-linking structure of the shell, which allowed acetone to easily penetrate the resulting hollow particles. In Comparative Example 3, the content of crosslinkable monomers in the first polymerizable monomer was low, and furthermore, a large amount of unreacted non-crosslinkable monomers remained. As a result, the crosslinking structure of the shell was rough, and it is presumed that the resulting hollow particles were easily permeated with acetone. In Comparative Example 4, instead of using a hydrophilic monomer with a solubility of 0.3 g / L or more in distilled water at 20°C as the second polymerizable monomer, styrene with a solubility of 0.2 g / L in distilled water at 20°C was used. As a result, the second polymerizable monomer was not easily incorporated into the shell, leaving unreacted polymerizable functional groups in the shell. This resulted in a rough cross-linking structure of the shell, which is presumed to have made the resulting hollow particles more susceptible to acetone penetration.

[0125] In contrast, the thermal conductivity modifiers in the form of hollow particles obtained in Examples 1 to 8 contained a polymer in the shell that contained 80 parts by mass or more of crosslinkable monomer units per 100 parts by mass of total monomer units, and the amount of hollow particles that precipitated in acetone in the above immersion test was less than 5% by mass. In Examples 1 to 8, the first polymerizable monomer contained in the mixture contained a sufficient amount of crosslinkable monomers per 100 parts by mass of the first polymerizable monomer, and in the polymerization process, when the polymerization conversion rate of the first polymerizable monomer reached 93% by mass or more, a second polymerizable monomer with a solubility of 0.3 g / L or more in distilled water at 20°C was added and subjected to further polymerization. Therefore, although a large amount of crosslinkable monomers were used, almost no unreacted polymerizable functional groups remained in the shell, and the crosslinked structure of the shell became dense, so it is presumed that hollow particles that are difficult for acetone to penetrate were obtained.

[0126] [Examples 9-17, Comparative Examples 5-8] (1) Preparation of resin composition (varnish) 50 parts epoxy resin (manufactured by Daicel Corporation, product code: EHPE3150CE), 24.9 parts curing agent (manufactured by DIC Corporation, product code: LF6161, 65% solids MEK solution), 0.1 parts 2-ethyl-4-methylimidazole (manufactured by Nacalai Tesque Corporation, 2E4MZ) as a curing catalyst, and the amount of methyl ethyl ketone (MEK) shown in Table 3 were added and stirred at room temperature for 30 minutes. After stirring, the amount of hollow particles, which are thermal conductivity modifiers obtained in Examples 1-8 or Comparative Examples 1-4, shown in Table 3 were added and stirred for a further 1 hour to prepare a resin composition (varnish) with a solids content of approximately 70%.

[0127] (2) Fabrication of molded products 15g of the varnish obtained above was placed on copper foil, degassed in a 130°C vacuum dryer until no more bubbles formed, and cured in a 110°C hot air circulating oven for 2 hours. Then, heated and pressurized at 0.5 MPa in a 110°C press, the temperature was increased to 205°C (4°C / min) and held for 1 hour, after which it was removed from the press to produce a plate-shaped molded body. The molded body was cut into a shape of 20mm × 40mm × 0.5mm to be used as a measuring plate.

[0128] [Comparative Example 9] 50 parts epoxy resin (manufactured by Daicel Corporation, product code: EHPE3150CE), 24.9 parts hardener (manufactured by DIC Corporation, product code: LF6161, 65% solids MEK solution), 0.1 parts 2-ethyl-4-methylimidazole (manufactured by Nacalai Tesque Corporation, 2E4MZ) as a curing catalyst, and 20 parts methyl ethyl ketone (MEK) were added and stirred at room temperature for 30 minutes to prepare a resin composition (varnish). Using the obtained varnish, molded bodies were prepared in the same procedure as in Examples 9-17 and Comparative Examples 5-8, and the molded bodies were cut into a shape of 20 mm × 40 mm × 0.5 mm to serve as measuring molded plates.

[0129] [evaluation] 6. Thermal conductivity The thermal conductivity of the molded test plates was measured using a rapid thermal conductivity meter (QTM-500, manufactured by Kyoto Electronics Manufacturing Co., Ltd.) and thin-film measurement software (SOFT-QTM5W, manufactured by Kyoto Electronics Manufacturing Co., Ltd.) under the following test conditions, using the transient thin-wire heating method. Table 3 shows the average thermal conductivity of two molded test plates prepared using the same procedure. (Test conditions) • Probe: PD-11 • Reference plate: Expanded polyethylene

[0130] 7.Reflectance The reflectance of the molded plate used for the thermal conductivity measurement described above was measured in the region from 320 nm to 820 nm using a UV spectrophotometer (Shimadzu Corporation, UV-VIS-NIR Spectrophotometer, UV-3600). Table 3 shows the average reflectance of two molded plates prepared using the same procedure at 420 nm, 580 nm, and 700 nm.

[0131] [Table 3]

[0132] [Consideration] As shown in Table 3 above, the molded articles of Comparative Examples 5 to 8, obtained using resin compositions containing 20% ​​by mass (41.7% by volume) of the thermal conductivity modifier of Comparative Examples 1 to 4, had a thermal conductivity of 0.189 to 0.199 W / m·K. This was only a reduction of 0.003 to 0.013 W / m·K compared to the molded article of Comparative Example 9 (thermal conductivity: 0.202 W / m·K) which did not contain the thermal conductivity modifier. In contrast, the molded article of Example 9, obtained using a resin composition containing 10% by mass (24.1% by volume) of the thermal conductivity modifier of Example 1, had a thermal conductivity of 0.175 W / m·K, even though it contained less thermal conductivity modifier than Comparative Examples 1-4. This was 0.027 W / m·K lower than the molded article of Comparative Example 9, which did not contain a thermal conductivity modifier. The molded articles of Examples 10-17, obtained using resin compositions containing 20% ​​by mass (41.7% by volume) of the thermal conductivity modifier of Examples 1-8, had a thermal conductivity of 0.142-0.150 W / m·K, which was 0.052-0.060 W / m·K lower than the molded article of Comparative Example 9, which did not contain a thermal conductivity modifier. As shown in Table 2 above, the thermal conductivity modifiers of Comparative Examples 1 to 4 had more than 5% by mass of hollow particles precipitated in acetone during the immersion test, and it is presumed that they were easily crushed due to the rough cross-linking structure of the shell. Therefore, in the molded articles of Comparative Examples 5 to 8 containing the thermal conductivity modifiers of Comparative Examples 1 to 4, it is presumed that the thermal conductivity was not sufficiently reduced because the hollow particle form of the thermal conductivity modifier was crushed during the manufacturing process of the molded articles, and the voids were not maintained. In contrast, the thermal conductivity modifiers of Examples 1 to 8, as shown in Table 2 above, contain a large number of crosslinkable monomer units in their shells, and the amount of hollow particles precipitated in acetone in the immersion test was less than 5% by mass. This suggests that the crosslinking structure of the shells was dense and therefore difficult to crush. Consequently, in the molded articles of Examples 9 to 17 containing the thermal conductivity modifiers of Examples 1 to 8, it is presumed that the thermal conductivity modifiers in the form of hollow particles were difficult to crush during the manufacturing process of the molded articles, and the voids were maintained, resulting in a sufficient reduction in thermal conductivity. Furthermore, comparing Examples 9 and 10, it was found that the higher the content of the thermal conductivity modifier, the lower the thermal conductivity of the molded body. Comparing Examples 10 and 11, it was found that the higher the porosity of the thermal conductivity modifier, the lower the thermal conductivity of the molded body. Comparing Examples 10, 12, and 13, the higher the content of crosslinkable monomer units in the shell of the thermal conductivity modifier, the lower the thermal conductivity of the molded body. This is presumed to be because a higher content of crosslinkable monomer units in the shell resulted in a denser crosslinking structure, improving the solvent resistance and strength of the thermal conductivity modifier. Comparing Examples 10 and 14-17, the thermal conductivity of the molded article differed depending on the type of second polymerizable monomer used in the preparation of the thermal conductivity modifier. When alkyl acrylates having an alkyl group with 1 to 4 carbon atoms were used as the second polymerizable monomer, there was a tendency for the thermal conductivity to decrease. Furthermore, the molded articles obtained in Examples 9 and 10 showed higher reflectivity across a wider wavelength range compared to the molded article of Comparative Example 9, which did not contain a thermal conductivity modifier. In particular, the reflectivity increased in the 420-780 nm wavelength range, especially in the 500-780 nm wavelength range. The reflectivity results for Examples 9 and 10 showed a tendency for reflectivity to increase with increasing thermal conductivity modifier content. The increased reflectivity of the molded articles in Examples 9 and 10 is thought to be due to the thermal conductivity modifier having voids, which efficiently reflected visible light due to the difference between the refractive index of the polymer shell (generally around 1.3-1.5) and the refractive index of the air, nitrogen, or vacuum inside the voids (1.0). It is also estimated that the molded articles of Examples 11-17, which contain the same amount of thermal conductivity modifier with similar volume-average particle size and void ratio as Example 10, will have reflectivity similar to that of Example 10. [Explanation of Symbols]

[0133] 1 Aqueous medium 2 Low polarity material 3. Dispersion stabilizer 4. Monomer composition 4a Hydrocarbon solvents 4b Materials other than hydrocarbon solvents 4c Polymerizable monomers dispersed in an aqueous medium 5. Oil-soluble polymerization initiators 6 Shells 8 Hollow part 10 droplets 20 Hollow particles containing hydrocarbon solvents in their hollow sections (second precursor particles) 100 Hollow particles with a hollow space filled with gas

Claims

1. A thermal conductivity modifier in the form of hollow particles comprising a resin-containing shell and a hollow portion surrounded by the shell, The hollow particles have a porosity of 60-80% and a volume-average particle size of 5.0-15.0 μm. The shell contains a polymer as the resin comprising hydrophilic non-crosslinked monomer units derived from a hydrophilic non-crosslinked monomer having a solubility of 0.3 g / L or more in distilled water at 20°C, and crosslinked monomer units. In 100 parts by mass of the total monomer units of the polymer, the content of the hydrophilic non-crosslinkable monomer units is 2 to 20 parts by mass, and the content of the crosslinkable monomer units is 80 to 98 parts by mass. The hydrophilic non-crosslinked monomer is at least one selected from the group consisting of alkyl (meth)acrylates having an alkyl group having 1 to 5 carbon atoms, and nitrile (meth)acrylate. The aforementioned crosslinkable monomer units consist solely of crosslinkable monomer units derived from (meth)acrylic crosslinkable monomers having a (meth)acryloyl group as a polymerizable functional group. The crosslinkable monomer unit comprises a difunctional crosslinkable monomer unit derived from a difunctional crosslinkable monomer and a trifunctional or higher crosslinkable monomer unit derived from a trifunctional or higher crosslinkable monomer, wherein the content of the trifunctional or higher crosslinkable monomer unit is 5 to 50 parts by mass in 100 parts by mass of the total monomer units of the polymer. The aforementioned bifunctional crosslinkable monomer is at least one selected from the group consisting of ethylene glycol di(meth)acrylate and pentaerythritol di(meth)acrylate. The crosslinkable monomer with three or more functions is at least one selected from the group consisting of trimethylolpropane tri(meth)acrylate and pentaerythritol tetra(meth)acrylate. The polymer content is 90% by mass or more of the total solid content of the shell (100% by mass), The amount of unreacted polymerizable monomers remaining relative to the solid content mass of the hollow particles is 750 ppm or less. A thermal conductivity modifier in which, in an immersion test in which 0.1 mg of the thermal conductivity modifier is added to 4 mL of acetone at a temperature of 25°C, shaken for 10 minutes at a shaking speed of 100 rpm, and then allowed to stand for 48 hours, the amount of thermal conductivity modifier that precipitates in the acetone is less than 5% by mass.

2. The thermal conductivity modifier according to claim 1, wherein, in 100 parts by mass of the total monomer units of the polymer, the content of the hydrophilic non-crosslinkable monomer units is 4.8 to 18.5 parts by mass, and the content of the crosslinkable monomer units is 81.5 to 95.2 parts by mass.

3. A molded article containing the thermal conductivity modifier described in claim 1 or 2.

Citation Information

Patent Citations

  • Ink composition

    JP2010222492A

  • Hollow particle and applications thereof

    JP2017066351A

  • Hollow particles and use of same

    WO2017163439A1

  • Hollow particles, method for producing same, and usage of same

    WO2019177006A1

  • Hollow-particle dispersion

    WO2019177013A1